Organic film forming material, substrate, organic film forming method, pattern forming method and organic film forming compound

By using compounds and other additives for forming organic films with imide structures in air or passive gases, the shortcomings of organic films in the prior art are solved in the heat resistance and landfill characteristics under high temperature conditions, and efficient Semiconductor device manufacturing.

CN113433796BActive Publication Date: 2024-12-13SHIN ETSU CHEMICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110308097.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-23
Filing Date
2021-03-23
Publication Date
2024-12-13
Estimated Expiration
2041-03-23

AI Technical Summary

Technical Problem

The prior art is difficult to form an organic film with high heat resistance, landfill characteristics and planarization characteristics under high temperature conditions, and it is prone to corrosion during the film formation process in passive gas, affecting the manufacturing quality of semiconductor devices.

Method used

An organic film formation compound containing a specific imide structure was developed to form a hardened film in an air or passive gas environment by spin coating and heat treatment, combining acid generators, surfactants and crosslinking agents to enhance the film. Heat resistance and landfill/planarization characteristics.

Benefits of technology

An organic film with heat resistance, adhesion and high landfill/planarization characteristics under high temperature and passive gas conditions is realized, which improves the manufacturing yield of semiconductor devices and avoids substrate corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113433796B_ABST
    Figure CN113433796B_ABST
Patent Text Reader

Abstract

The present invention relates to an organic film-forming material, a substrate, an organic film-forming method, a pattern-forming method, and an organic film-forming compound. The subject of the present invention is to provide an organic film-forming compound that hardens not only under film-forming conditions in air but also under film-forming conditions in an inert gas, and can form an organic film that has excellent heat resistance, pattern filling and planarization characteristics formed on a substrate, and good adhesion to a substrate, and to provide an organic film-forming material containing the compound, and to provide a substrate, an organic film-forming method, and a pattern-forming method using the material. The means for solving the problem is an organic film-forming material, which contains (A) an organic film-forming compound represented by formula (1A), and (B) an organic solvent. #imgabs0# In the formula, W1 is a tetravalent organic group, n1 represents an integer of 0 or 1, n2 represents an integer of 1 to 3, and R1 represents an alkynyl group having 2 to 10 carbon atoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an organic film-forming material, a semiconductor device manufacturing substrate using the material, an organic film-forming method, a pattern-forming method using a multilayer resist method, and an organic film-forming compound that can be preferably used for the material. Background Art

[0002] In the past, the high integration and high speed of semiconductor devices were achieved by miniaturizing the pattern size by shortening the wavelength of the light source in the photolithography technology (optical lithography) using light exposure, which is a general technology. In order to form such a fine circuit pattern on a substrate (processed substrate) for semiconductor device manufacturing, a method of processing the processed substrate by dry etching using a photoresist film formed with a pattern as an etching mask is usually used. However, in reality, there is no dry etching method that can obtain complete etching selectivity between the photoresist film and the processed substrate, so in recent years, substrate processing using a multilayer resist method has been widely adopted. This method is to insert an intermediate film with different etching selectivity from the photoresist film (hereinafter referred to as the resist upper film) between the resist upper film and the processed substrate, and after the resist upper film obtains a pattern, the resist upper film pattern is used as a dry etching mask and the pattern is transferred to the intermediate film by dry etching, and then the intermediate film is used as a dry etching mask and the pattern is transferred to the processed substrate by dry etching.

[0003] As one of the multilayer resist methods, there is a three-layer resist method that can be performed using a general resist composition used in the single-layer resist method. This method is to apply an organic lower film material (hereinafter referred to as an organic film forming material) composed of a composition containing an organic resin on a substrate to be processed and calcine it to form an organic lower film (hereinafter referred to as an organic film), and then apply a resist intermediate film material (hereinafter referred to as a silicon-containing resist intermediate film material) composed of a composition containing a silicon-containing resin and calcine it to form a silicon-containing film (hereinafter referred to as a silicon-containing resist intermediate film), and then form a general organic photoresist film (hereinafter referred to as a resist upper film) thereon. After the resist upper film is patterned, if dry etching is performed using fluorine-based gas plasma, the organic resist upper film can obtain a good etching selectivity ratio relative to the silicon-containing resist intermediate film, so the resist upper film pattern can be transferred to the silicon-containing resist intermediate film. According to this method, even if a resist upper film that does not have a sufficient film thickness required for directly processing a substrate to be processed or a resist upper film that does not have sufficient dry etching resistance required for processing a substrate to be processed is used, since the silicon-containing resist intermediate film is generally of the same or thinner film thickness as the resist upper film, the pattern can still be easily transferred to the silicon-containing resist intermediate film. Then, the silicon-containing resist intermediate film to which the pattern has been transferred is used as a dry etching mask and the pattern is transferred to the organic film by dry etching using oxygen-based or hydrogen-based gas plasma, so that the pattern can be transferred to the organic film having sufficient dry etching resistance required for processing the substrate. The organic film pattern obtained after the pattern is transferred by dry etching using fluorine-based gas, chlorine-based gas, etc. can be transferred to the substrate.

[0004] On the other hand, the miniaturization in the manufacturing steps of semiconductor devices is gradually approaching the essential limit of the wavelength of the light source for optical lithography. Therefore, in recent years, some people have studied the high integration of semiconductor devices that do not rely on miniaturization. As one of the methods, some people have studied semiconductor devices with complex structures such as multi-gate structures, and some of them have been put into practical use. When forming such a structure by a multilayer resist method, an organic film forming material can be used that can fill the holes, trenches, fins and other tiny patterns formed on the processed substrate with a film without gaps, or can fill the height difference, pattern-dense parts and non-patterned areas with a film and flatten them (planarization). By using such an organic film forming material to form a flat organic film surface on a high-low difference substrate, the film thickness variation of the silicon-containing resist intermediate film and the resist upper film formed thereon can be suppressed, and the focus margin of optical lithography can be suppressed. The reduction of tolerance in the subsequent processing steps of the processed substrate can be suppressed. Thereby, semiconductor devices can be manufactured with a good yield. On the other hand, in the single-layer resist method, the thickness of the upper resist film increases in order to fill the processed substrate with height differences and patterns. This causes the pattern to collapse after exposure and development, and the pattern shape to deteriorate due to reflection from the substrate during exposure. The pattern formation margin during exposure becomes narrower, making it difficult to manufacture semiconductor devices with a good yield.

[0005] In addition, as for the method of increasing the speed of semiconductor devices of the next generation, for example, some people have begun to study the use of novel materials with high electron mobility such as strained silicon and gallium arsenide, and precision materials such as ultra-thin film polysilicon controlled in angstroms. However, when a substrate to be processed using such novel precision materials is formed with a planarization film using the above-mentioned organic film forming material, for example, under film forming conditions in air at a temperature of 300°C or above, the material may be corroded by oxygen in the air, and the performance of the original material design may not be exerted at the high speed of the semiconductor device, and the yield required for industrial production may not be achieved. Therefore, in order to avoid the reduction in yield caused by corrosion of the substrate by air under such high temperature conditions, an organic film forming material that can be formed in a passive gas is desired.

[0006] In the past, condensation resins obtained by using carbonyl compounds such as ketones, aldehydes, and aromatic alcohols as condensing agents for phenolic and naphthol compounds are known as materials for forming organic films for multilayer resist methods. For example, the fluorene bisphenol novolac resins described in Patent Document 1, the bisphenol compounds and novolac resins thereof described in Patent Document 2, the novolac resins of adamantane phenol compounds described in Patent Document 3, and the bisnaphthol compounds and novolac resins thereof described in Patent Document 4 can be exemplified. Such materials can be formed into films having solvent resistance to the coating film material used in the next step due to the crosslinking using a hydroxymethyl compound as a crosslinking agent, the oxidation of the α position of the aromatic ring due to the action of oxygen in the air, and the curing effect caused by the crosslinking reaction by the subsequent condensation.

[0007] In addition, materials using triple bonds as intermolecular crosslinking groups of curable resins are known. For example, Patent Documents 5 to 10 are known. These materials form a cured film having solvent resistance not only through the crosslinking from the aforementioned hydroxymethyl group but also through the crosslinking caused by the polymerization of triple bonds. However, these organic film-forming materials are not sufficient in terms of the embedding characteristics and planarization characteristics of the pattern formed on the substrate.

[0008] In addition, with respect to examples of compounds having an imide structure, there are known resins having a polyimide structure as described in Patent Documents 11 and 12, and Patent Document 13 which uses a compound having a bismaleimide structure, but the formation of a cured film in a passive gas, the change in film thickness due to thermal decomposition under high temperature conditions, the filling characteristics, the planarization characteristics, etc. are not known.

[0009] Prior art literature

[0010] Patent Literature

[0011] [Patent Document 1] Japanese Patent Application Publication No. 2005-128509

[0012] [Patent Document 2] Japanese Patent Application Publication No. 2006-293298

[0013] [Patent Document 3] Japanese Patent Application Publication No. 2006-285095

[0014] [Patent Document 4] Japanese Patent Application Publication No. 2010-122656

[0015] [Patent Document 5] Japanese Patent Application Publication No. 2010-181605

[0016] [Patent Document 6] WO2014-208324

[0017] [Patent Document 7] Japanese Patent Application Publication No. 2012-215842

[0018] [Patent Document 8] Japanese Patent Application Publication No. 2016-044272

[0019] [Patent Document 9] Japanese Patent Application Publication No. 2016-060886

[0020] [Patent Document 10] Japanese Patent Application Publication No. 2017-119671

[0021] [Patent Document 11] Japanese Patent Application Publication No. 2013-137334

[0022] [Patent Document 12] WO2019-146378

[0023] [Patent Document 13] WO2018-212116 Summary of the invention

[0024] Problem that the invention aims to solve

[0025] The present invention is made in view of the above facts, and its purpose is to provide a compound for forming an organic film, which can harden not only under film forming conditions in air, but also under film forming conditions in an inert gas, and can form an organic film having excellent heat resistance, pattern filling and planarization characteristics formed on a substrate, and good adhesion to the substrate, and a material for forming an organic film containing the compound. Furthermore, the purpose of the present invention is also to provide a substrate for manufacturing a semiconductor device, a method for forming an organic film, and a method for forming a pattern using the material.

[0026] Solutions for solving problems

[0027] In order to solve the above-mentioned problems, the present invention provides an organic film-forming material, characterized in that it contains: (A) an organic film-forming compound represented by the following general formula (1A), and (B) an organic solvent;

[0028] [Chemistry 1]

[0029]

[0030] In the formula, W1 is a tetravalent organic group, n1 represents an integer of 0 or 1, n2 represents an integer of 1 to 3, and R1 represents an alkynyl group having 2 to 10 carbon atoms.

[0031] If it is such an organic film forming material, it will harden not only under film forming conditions in air, but also under film forming conditions in inert gas, and can form an organic film having high heat resistance, good adhesion to the substrate, and a high degree of filling / planarization properties.

[0032] The component (A) is preferably a compound represented by the following general formula (1B).

[0033] [Chemistry 2]

[0034]

[0035] In the formula, W2 is an oxygen atom or a divalent group, and n1, n2 and R1 are the same as described above.

[0036] From the viewpoint of imparting excellent heat resistance, the organic film-forming compound as the component (A) preferably has the above-mentioned structure.

[0037] W2 in the general formula (1B) is preferably a divalent organic group having at least one aromatic ring.

[0038] By containing such an organic film-forming compound as the component (A), more excellent heat resistance can be achieved.

[0039] The component (A) is preferably a compound represented by the following general formula (1C).

[0040] [Chemistry 3]

[0041]

[0042] In the formula, W3 is a divalent organic group, n3 represents an integer of 0 or 1, and n1, n2 and R1 are the same as described above.

[0043] The organic film-forming compound as the component (A) preferably has the above-mentioned structure from the viewpoint of solubility in an organic solvent and imparting thermal fluidity.

[0044] The component (A) is preferably a compound represented by the following general formula (1D).

[0045] [Chemistry 4]

[0046]

[0047] In the formula, n3 represents an integer of 0 or 1, and n2 and R1 are the same as described above.

[0048] When the organic film-forming compound as the component (A) has the above-mentioned structure, it is preferably the above-mentioned structural formula from the viewpoint of improving various physical properties such as heat resistance, solvent solubility, and flatness.

[0049] The ratio Mw / Mn of the weight average molecular weight Mw and the number average molecular weight Mn of the component (A) in terms of polystyrene obtained by gel permeation chromatography is preferably 1.00≤Mw / Mn≤1.10.

[0050] By controlling the Mw / Mn of the organic film-forming compound as the component (A) within such a range, an organic film having excellent filling characteristics and flatness can be formed.

[0051] The organic solvent is preferably a mixture of one or more organic solvents having a boiling point of less than 180°C and one or more organic solvents having a boiling point of 180°C or higher.

[0052] The organic film forming material of the organic solvent is a mixture as described above, and the addition of the high boiling point solvent imparts thermal fluidity, thereby providing an organic film having both higher filling and planarizing properties.

[0053] Furthermore, the organic film-forming material of the present invention may further contain one or more of (C) an acid generator, (D) a surfactant, (E) a crosslinking agent, and (F) a plasticizer.

[0054] The organic film-forming material of the present invention may contain one or more of the above-mentioned components (C) to (F) depending on the purpose.

[0055] The present invention also provides a substrate for manufacturing a semiconductor device, wherein an organic film is formed on the substrate by curing the organic film-forming material of the present invention.

[0056] Such a substrate includes an organic film having high heat resistance, good adhesion to the substrate, and high filling / planarization properties. Therefore, if it is used in the manufacturing process of a semiconductor device, the yield of the semiconductor device will be improved.

[0057] In addition, the present invention provides a method for forming an organic film, which is an organic film forming method suitable for the manufacturing steps of a semiconductor device, characterized in that: the organic film forming material of the present invention is spin-coated on a substrate to be processed, and the substrate to be processed coated with the organic film forming material is heat-treated at a temperature of 50° C. to 600° C. in an inert gas environment for a period of 5 seconds to 7200 seconds to obtain a cured film.

[0058] The organic film formed by the method of the present invention and suitable for the manufacturing steps of semiconductor devices will still harden even if the film is formed in a passive gas, and has high heat resistance and a high degree of filling / planarization characteristics. If it is used in the manufacturing steps of semiconductor devices, the yield of the semiconductor devices will become good.

[0059] The present invention also provides a method for forming an organic film, which is an organic film forming method suitable for the manufacturing step of a semiconductor device, characterized in that: the organic film forming material of the present invention is spin-coated on a substrate to be processed, the substrate to be processed coated with the organic film forming material is heat-treated in air at a temperature of 50° C. to 300° C. for a period of 5 seconds to 600 seconds to form a coating film, and then heat-treated in an inert gas environment at a temperature of 200° C. to 600° C. for a period of 10 seconds to 7200 seconds to obtain a cured film.

[0060] The organic film formed by the method of the present invention and suitable for the manufacturing steps of semiconductor devices will still harden even if the film is formed in a passive gas, and has high heat resistance and a high degree of filling / planarization characteristics. If it is used in the manufacturing steps of semiconductor devices, the yield of the semiconductor devices will become good.

[0061] In addition, at this time, the oxygen concentration in the inert gas is preferably 1% or less.

[0062] The organic film forming material of the present invention can be sufficiently hardened without generating sublimates even when heated in such an inert gas environment, and can form an organic film having excellent adhesion to the substrate. Furthermore, by heating in such an inert gas environment, corrosion of the substrate to be processed can be prevented.

[0063] As the substrate to be processed, a substrate to be processed having a structure with a height of 30 nm or more or a height difference can be used.

[0064] The method for forming an organic film of the present invention is particularly useful for forming a flat organic film on such a substrate to be processed.

[0065] Furthermore, the present invention provides a pattern forming method, characterized in that an organic film is formed on a workpiece using the organic film forming material of the present invention, a silicon-containing resist intermediate film is formed on the organic film using a silicon-containing resist intermediate film material, a resist upper film is formed on the silicon-containing resist intermediate film using a photoresist composition, a circuit pattern is formed on the resist upper film, the resist upper film with the pattern formed is used as a mask to etch the aforementioned silicon-containing resist intermediate film, and the pattern is transferred to the silicon-containing resist intermediate film, the silicon-containing resist intermediate film with the pattern transferred is used as a mask to etch the aforementioned organic film, and the pattern is transferred to the organic film, and the organic film with the pattern transferred is further used as a mask to etch the aforementioned workpiece, and the pattern is transferred to the workpiece.

[0066] In addition, the present invention provides a pattern forming method, which is characterized by: forming an organic film on a workpiece using the organic film forming material of the present invention, forming a silicon-containing resist intermediate film on the organic film using a silicon-containing resist intermediate film material, forming an organic anti-reflective film on the silicon-containing resist intermediate film, forming a resist upper film using a photoresist composition on the organic anti-reflective film, and forming a four-layer film structure, forming a circuit pattern on the resist upper film, using the resist upper film with the pattern formed as a mask and etching the aforementioned organic anti-reflective film and the aforementioned silicon-containing resist intermediate film, and transferring the pattern to the organic anti-reflective film and the silicon-containing resist intermediate film, using the silicon-containing resist intermediate film with the pattern transferred as a mask and etching the aforementioned organic film, and transferring the pattern to the aforementioned organic film, further using the organic film with the pattern transferred as a mask and etching the aforementioned workpiece, and transferring the pattern to the workpiece.

[0067] In addition, the present invention provides a pattern forming method, which is characterized by: forming an organic film on a workpiece using the organic film forming material of the present invention, forming an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the organic film, forming a resist upper film on the inorganic hard mask using a photoresist composition, forming a circuit pattern on the resist upper film, using the resist upper film with the pattern formed as a mask and etching the aforementioned inorganic hard mask to transfer the pattern to the inorganic hard mask, using the inorganic hard mask with the transferred pattern as a mask and etching the aforementioned organic film to transfer the pattern to the organic film, further using the organic film with the transferred pattern as a mask and etching the aforementioned workpiece to transfer the pattern to the workpiece.

[0068] In addition, the present invention provides a pattern forming method, which is characterized by: forming an organic film on a workpiece using the organic film forming material of the present invention, forming an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the organic film, forming an organic antireflection film on the inorganic hard mask, forming a resist upper film on the organic antireflection film using a photoresist composition to form a four-layer film structure, forming a circuit pattern on the resist upper film, using the resist upper film with the pattern formed as a mask and etching the organic antireflection film and the inorganic hard mask to transfer the pattern to the organic antireflection film and the inorganic hard mask, using the inorganic hard mask with the pattern transferred as a mask and etching the organic film to transfer the pattern to the organic film, further using the organic film with the pattern transferred as a mask and etching the workpiece to transfer the pattern to the workpiece.

[0069] The organic film forming material of the present invention can be preferably used in various pattern forming methods such as three-layer resist processing using a silicon-containing resist intermediate film or an inorganic hard mask, and four-layer resist processing using an organic anti-reflection film in addition to these. If a circuit pattern is formed by such a pattern forming method of the present invention in the manufacturing step of a semiconductor device, the semiconductor device can be manufactured with a good yield.

[0070] At this time, the inorganic hard mask is preferably formed by a CVD method or an ALD method.

[0071] In the pattern forming method of the present invention, for example, an inorganic hard mask can be formed by using such a method.

[0072] In this case, in forming the circuit pattern, it is preferable to form the circuit pattern by photolithography using light with a wavelength of 10 nm to 300 nm, direct drawing using an electron beam, nanoimprinting, or a combination thereof.

[0073] In the formation of the aforementioned circuit pattern, the circuit pattern is preferably developed using an alkali or an organic solvent.

[0074] In the pattern forming method of the present invention, such a circuit pattern forming method and a developing method can be preferably used.

[0075] Furthermore, as the aforementioned processed body, it is preferable to use a semiconductor device substrate, or a film obtained by forming any one of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film on the semiconductor device substrate.

[0076] As the aforementioned workpiece, it is preferable to use one containing silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof.

[0077] According to the pattern forming method of the present invention, the above-mentioned object to be processed can be processed to form a pattern.

[0078] The present invention also provides an organic film-forming compound represented by the following general formula (1A).

[0079] [Chemistry 5]

[0080]

[0081] In the formula, W1 is a tetravalent organic group, n1 represents an integer of 0 or 1, n2 represents an integer of 1 to 3, and R1 represents an alkynyl group having 2 to 10 carbon atoms.

[0082] If it is such a compound having an imide structure, it will harden not only under film formation conditions in air, but also under film formation conditions in an inert gas, and can form an organic film forming compound that has high heat resistance, good adhesion to the substrate, and a high degree of filling / planarization properties.

[0083] The organic film-forming compound is preferably represented by the following general formula (1B).

[0084] [Chemistry 6]

[0085]

[0086] In the formula, W2 is an oxygen atom or a divalent group, and n1, n2 and R1 are the same as described above.

[0087] Such a compound has curability not only under film formation conditions in air but also under film formation conditions in an inert gas, and can exhibit more excellent heat resistance under any of the above film formation conditions.

[0088] W2 in the general formula (1B) is preferably a divalent organic group having at least one aromatic ring.

[0089] Such a compound can express even more excellent heat resistance.

[0090] The organic film-forming compound is preferably represented by the following general formula (1C).

[0091] [Chemistry 7]

[0092]

[0093] In the formula, W3 is a divalent organic group, n3 represents an integer of 0 or 1, and n1, n2 and R1 are the same as described above.

[0094] Such a compound can impart solvent solubility without impairing heat resistance.

[0095] The organic film-forming compound is preferably represented by the following general formula (1D).

[0096] [Chemistry 8]

[0097]

[0098] In the formula, n3 represents an integer of 0 or 1, and n2 and R1 are the same as described above.

[0099] Such a compound can suppress film shrinkage during curing and can be a compound for forming an organic film having excellent filling / planarizing properties.

[0100] Effects of the Invention

[0101] As described above, the organic film forming compound of the present invention is a compound that hardens and does not produce byproducts even under film forming conditions in a passive gas that prevents corrosion of the substrate, and is useful when used to form an organic film having high heat resistance, good adhesion to the substrate, and a high degree of embedding and planarization characteristics. In addition, the organic film forming material containing this compound is a material that forms an organic film having excellent embedding / planarization characteristics and having various characteristics such as heat resistance and etching resistance. Therefore, if it is an organic film obtained by using the organic film forming material of the present invention, it is an organic film having a high degree of embedding / planarization characteristics, so that there will be no micropores caused by poor embedding and unevenness on the surface of the organic film caused by insufficient flatness. Therefore, the organic film forming material of the present invention is extremely useful as an organic film forming material in a multilayer resist method such as a two-layer resist method, a three-layer resist method using a silicon-containing intermediate film, and a four-layer resist method using a silicon-containing intermediate film and an organic anti-reflection film, or a planarization material for semiconductor device manufacturing. In addition, the organic film formed by the organic film forming material of the present invention has excellent heat resistance, so even when a CVD hard mask is formed on the organic film, there is no change in film thickness due to thermal decomposition, and it is suitable for pattern formation. Furthermore, the semiconductor device substrate flattened by the organic film of the present invention has a wider process margin during patterning, and the semiconductor device can be manufactured with a good yield. Moreover, if a circuit pattern is formed by the pattern forming method of the present invention in the manufacturing step of the semiconductor device, the semiconductor device can be manufactured with a good yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0102] [ Figure 1 ] is an illustration of the flattening characteristics of the present invention.

[0103] [ Figure 2 ] is an explanatory diagram of an example of a pattern forming method utilizing a three-layer resist method of the present invention.

[0104] [ Figure 3 ] is an explanatory diagram of the landfill characteristic evaluation method in the embodiment.

[0105] [ Figure 4 ] is an explanatory diagram of the flattening characteristic evaluation method in the embodiment. DETAILED DESCRIPTION

[0106] As described above, in order to prevent corrosion of the substrate, it is sought to develop an organic film-forming compound that does not generate byproducts even under film-forming conditions in an inert gas, for example, at 300° C. or higher, and can form an organic film that has excellent filling and planarization properties of a pattern formed on a substrate and good dry etching resistance during substrate processing. Furthermore, it is sought to develop an organic film-forming material that does not cause a change in the film thickness of the organic film due to thermal decomposition even when a CVD hard mask is formed on the organic film, and an organic film-forming compound that is useful for a pattern forming method using the material.

[0107] Usually, when forming an organic film, an organic film-forming compound is dissolved in an organic solvent to form a composition, which is then applied to a substrate on which a structure, wiring, etc. of a semiconductor device are formed, and calcined to form an organic film. When the composition is just applied, a coating film conforming to the shape of the height difference structure on the substrate is formed, but when the coating film is calcined, most of the organic solvent evaporates before hardening occurs, and an organic film is formed from the organic film-forming compound remaining on the substrate. The inventors of the present application and others have thought that if the organic film-forming compound remaining on the substrate at this time has sufficient thermal fluidity, the thermal flow can be used to flatten the height difference shape just after coating and form a flat film.

[0108] The inventors of the present application have further discovered that an organic film-forming compound having an imide structure represented by the following general formula (1A) has the same thermal curability as known organic film-forming materials in air or inert gas due to the action of the alkynyl-containing group represented by OR1, and produces no by-products during the curing reaction using the cross-linking group, i.e., the alkynyl group containing a triple bond represented by R1. The organic film-forming material has good thermal fluidity and thus has a high degree of filling / planarization properties, good dry etching resistance, and heat resistance such that there is no change in the coating film thickness due to thermal decomposition even when a CVD hard mask is formed. The present invention is thus completed.

[0109] That is, the present invention is an organic film-forming compound represented by the following general formula (1A).

[0110] [Chemistry 9]

[0111]

[0112] In the formula, W1 is a tetravalent organic group, n1 represents an integer of 0 or 1, n2 represents an integer of 1 to 3, and R1 represents an alkynyl group having 2 to 10 carbon atoms.

[0113] The present invention is also directed to an organic film-forming material, characterized by comprising: (A) an organic film-forming compound represented by the above-mentioned general formula (1A), and (B) an organic solvent.

[0114] The present invention is described in detail below, but the present invention is not limited thereto.

[0115] <Organic film-forming compound>

[0116] The organic film-forming compound of the present invention is an organic film-forming compound having an imide structure represented by the following general formula (1A).

[0117] [Chemistry 10]

[0118]

[0119] In the formula, W1 is a tetravalent organic group, n1 represents an integer of 0 or 1, n2 represents an integer of 1 to 3, and R1 represents an alkynyl group having 2 to 10 carbon atoms.

[0120] By forming a closed-loop imide structure as in the general formula (1A) above in advance, there will be no desorption reaction of water and the like generated as a byproduct when the imide precursor such as amic acid is closed, the film shrinkage is suppressed, the flatness of the organic film is not damaged, and the decomposition caused by the equilibrium reaction of the imide precursor can be suppressed, and the storage stability is also excellent. OR1 acts as a substituent that imparts hardening properties in the atmosphere and in the presence of inert gases, and the chain length can be appropriately adjusted from the perspectives of imparting flatness and hardening properties. Furthermore, by appropriately selecting the structure of the linking group portion represented by W1, various physical properties such as etching resistance and optical properties can be adjusted. In addition, the imide structure contributes to imparting heat resistance and also contributes to improving the adhesion to the substrate. By improving the adhesion, film peeling can be prevented when an inorganic hard mask obtained using a CVD method or an ALD method is formed directly above the organic film, and an organic film with excellent process margin can be formed.

[0121] The partial structure having an imide ring including W1 in (1A) in the above general formula can be exemplified by the following, and such aromatic ring may have a substituent, and examples thereof include an alkyl group having 1 to 10 carbon atoms, an alkynyl group and an alkenyl group having 3 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, a nitro group, a halogen group, a nitrile group, an alkoxycarbonyl group having 1 to 10 carbon atoms, and an alkanoyloxy group having 1 to 10 carbon atoms. Among them, those having a naphthalene ring with n1=1 are preferred from the viewpoint of heat resistance and curability.

[0122] [Chemistry 11]

[0123]

[0124] The substituent OR1 in the general formula (1A) functions as a thermosetting group, and the following are exemplified. Among them, propargyloxy is preferred from the viewpoint of curability, heat resistance, and availability of raw materials.

[0125] [Chemistry 12]

[0126]

[0127] In the above general formula, W1 can be exemplified by the following, and such aromatic ring may also have a substituent, and examples thereof include hydroxyl, trifluoromethyl, alkyl having 1 to 10 carbon atoms, alkynyl having 3 to 10 carbon atoms, alkenyl, alkyloxy having 1 to 10 carbon atoms, alkynyloxy having 3 to 10 carbon atoms, alkenyloxy, aryl having 6 to 10 carbon atoms, nitro, halogen, nitrile, alkoxycarbonyl having 1 to 10 carbon atoms, alkanoyloxy having 1 to 10 carbon atoms, and the like.

[0128] [Chemistry 13]

[0129]

[0130] [Chemistry 14]

[0131]

[0132] [Chemistry 15]

[0133]

[0134] [Chemistry 16]

[0135]

[0136] [Chemistry 17]

[0137]

[0138] [Chemistry 18]

[0139]

[0140] The compound for forming an organic film of the present invention preferably has a structure represented by the following general formula (1B).

[0141] [Chemistry 19]

[0142]

[0143] In the formula, W2 is an oxygen atom or a divalent group, and n1, n2 and R1 are the same as described above.

[0144] Such a compound has curability not only under film formation conditions in air but also under film formation conditions in an inert gas, and can exhibit more excellent heat resistance under any of the above film formation conditions.

[0145] W2 in the general formula (1B) is preferably any one of the following formulae: Among them, from the viewpoint of solvent solubility and fluidity, one or more of a hexafluoroisopropylidene group, an ether bond, a fluorene structure, and a dihydroindene structure are preferred.

[0146] [Chemistry 20]

[0147]

[0148] The aromatic ring in the above formula may have a substituent.

[0149] W2 in the above general formula (1B) is preferably a divalent organic group having at least one aromatic ring.

[0150] Such a compound can express even more excellent heat resistance.

[0151] The organic film-forming compound of the present invention preferably has a structure represented by the following general formula (1C).

[0152] [Chemistry 21]

[0153]

[0154] In the formula, W3 is a divalent organic group, n3 represents an integer of 0 or 1, and n1, n2 and R1 are the same as described above.

[0155] W3 in the general formula (1C) is preferably any one of the following formulae: Of these, a fluorene structure is more preferred from the viewpoints of film-forming property, solvent solubility, and heat resistance.

[0156] [Chemistry 22]

[0157]

[0158] The aromatic ring in the above formula may have a substituent.

[0159] The organic film-forming compound of the present invention is more preferably one having a structure represented by the following general formula (1D).

[0160] [Chemistry 23]

[0161]

[0162] In the formula, n2, n3 and R1 are the same as above.

[0163] Among the structures represented by the general formula (1D), those in which OR1 is a propargyloxy group located at the β-position of the naphthalene ring are particularly preferred.

[0164] [Chemistry 24]

[0165]

[0166] In the case where there is a propargyloxy group at the β position on the naphthalene ring as described above, it is believed that the propargyloxy group is baked to form a cyclized body as shown in the following formula, and then polymerized to show thermal curing properties. At this time, the propargyloxy group will impart fluidity before cyclization, and after cyclization, it will not only play a role as a curing group but also contribute to the improvement of heat resistance due to the formation of a ring structure. In the curing reaction at this time, decomposable additives such as thermal acid generators that become dissipated gas components, condensation reactions, and other byproducts are not produced, so the sublimation components during baking can be suppressed, and the film shrinkage can also be suppressed. Through these effects, heat resistance and filling / flattening characteristics, which are opposite properties, can be taken into account.

[0167] [Chemistry 25]

[0168]

[0169] The organic film-forming compound of the present invention is preferably an organic film-forming compound having a ratio Mw / Mn of a polystyrene-equivalent weight average molecular weight Mw to a number average molecular weight Mn of 1.00≤Mw / Mn≤1.10 as determined by gel permeation chromatography.

[0170] By controlling the Mw / Mn of the compound for forming an organic film within such a range, an organic film having excellent filling characteristics and flatness can be formed.

[0171] When the Mw / Mn ratio is within the above range, the thermal fluidity of the organic film-forming compound is further improved. Therefore, when the compound is added to the composition, an organic film can be formed that can not only well fill the fine structure formed on the substrate but also make the entire substrate flat.

[0172] [Method for producing organic film-forming compound]

[0173] As for the method of obtaining the organic film forming compound of the present invention, for example, it can be listed that after obtaining the amic acid compound (STEP1) by the reaction of tetracarboxylic dianhydride and aniline derivative as shown below, thermal imidization or chemical imidization (STEP2) is performed for synthesis. At this time, the tetracarboxylic dianhydride and aniline derivative used in the synthesis of the amic acid compound can be used alone or in combination of two or more. These can be appropriately selected and combined according to the required characteristics. W1, R1, n1 and n2 in the following formula are the same as above.

[0174] [Chemistry 26]

[0175] STEP1

[0176]

[0177] STEP 2

[0178]

[0179] In the synthesis of the amic acid represented in STEP 1, it can usually be obtained in an organic solvent at room temperature or under cooling or heating as needed. As for the solvent used, alcohols such as methanol, ethanol, isopropanol, butanol, ethylene glycol, propylene glycol, diethylene glycol, glycerol, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, diethyl ether, dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, 1,4-dioxane, ethers, dichloromethane, chloroform, dichloroethane, trichloroethylene, etc., chlorine-based solvents, hexane, heptane, benzene, toluene, xylene, Hydrocarbons such as cumene, nitriles such as acetonitrile, ketones such as acetone, ethyl methyl ketone, isobutyl methyl ketone, cyclohexanone, esters such as methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol methyl ether acetate, γ-butyrolactone, N-methyl-2-pyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, N,N-dimethylformamide, hexamethylphosphoric acid triamide, etc., can be used alone or in combination of two or more. These solvents can be used in the range of 0 to 2000 parts by mass relative to 100 parts by mass of the reaction raw materials, and the reaction temperature is preferably -50°C to about the boiling point of the solvent, preferably room temperature to 150°C. The reaction time is appropriately selected from 0.1 to 100 hours.

[0180] The synthesis of these can also use a base catalyst as needed, and the base catalyst can be sodium bicarbonate, sodium carbonate, potassium carbonate, calcium carbonate, cesium carbonate, sodium hydroxide, potassium hydroxide, sodium hydride, potassium phosphate and other inorganic base compounds, triethylamine, diisopropylethylamine, N, N-dimethylaniline, pyridine, 4-dimethylaminopyridine and other organic bases, which can be used alone or in combination of two or more. The amount used is 0.01 to 20 moles relative to the molar number of the acid dianhydride of the raw material, preferably in the range of 0.05 to 10 moles.

[0181] As for the reaction method, there are the following methods: adding tetracarboxylic dianhydride and aniline derivatives to the solvent at one time; adding tetracarboxylic dianhydride and aniline derivatives separately or mixing them and dispersing or dissolving them before adding them; after dispersing or dissolving any one of the acid dianhydride or aniline derivative in the solvent, adding the other one dispersed or dissolved in the solvent. In addition, when adding multiple types of tetracarboxylic dianhydride and aniline derivatives, they can be mixed in advance and reacted, or they can be reacted in sequence. When using an alkali catalyst, the alkali catalyst and the acid dianhydride or aniline derivative can be added at one time, and the alkali catalyst can be dispersed or dissolved in advance and then added. The obtained amic acid solution can also be subjected to the reaction of STEP2, can be used directly as a compound for organic film formation, or can be diluted with an organic solvent for separation, washing and recovery in order to remove unreacted raw materials, catalysts, etc. present in the system.

[0182] As for the organic solvent used for liquid separation and cleaning, there is no particular restriction as long as it is a soluble compound and can be separated into two layers when mixed with water. Examples include hydrocarbons such as hexane, heptane, benzene, toluene, and xylene, esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate, ketones such as methyl ethyl ketone, methyl amyl ketone, cyclohexanone, and methyl isobutyl ketone, ethers such as diethyl ether, diisopropyl ether, methyl tert-butyl ether, and ethyl cyclopentyl methyl ether, chlorine-based solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene, and mixtures thereof. As for the cleaning water used at this time, what is generally called deionized water or ultrapure water can be used. The number of cleaning times can be more than one time. Even if the cleaning is performed more than 10 times, the corresponding cleaning effect may not be obtained, so it is preferably about 1 to 5 times.

[0183] In order to remove the unreacted raw materials or acidic components in the system during liquid separation and washing, an alkaline aqueous solution can also be used for washing. Specifically, the base includes alkali metal hydroxides, alkali metal carbonates, alkaline earth metal hydroxides, alkaline earth metal carbonates, ammonia, and organic ammonium.

[0184] In addition, in order to remove unreacted raw materials, metal impurities or alkaline components in the system during liquid separation and washing, an acidic aqueous solution can also be used for washing. As the acid, specifically, inorganic acids such as hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and heteropoly acids, and organic acids such as oxalic acid, fumaric acid, maleic acid, trifluoroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid can be cited.

[0185] The above-mentioned liquid separation cleaning using alkaline aqueous solution and acidic aqueous solution may be performed alone or in combination. From the viewpoint of removing metal impurities, liquid separation cleaning is preferably performed in order of cleaning using alkaline aqueous solution and cleaning using acidic aqueous solution.

[0186] After the above-mentioned separation and washing using alkaline aqueous solution or acidic aqueous solution, neutral water can be used for washing. The washing number can be more than 1 time, preferably about 1 to 5 times. As neutral water, the above-mentioned deionized water, ultrapure water, etc. can be used. The washing number can be more than 1 time, but if the number is small, the alkaline component and the acidic component may not be removed. Even if washing is performed more than 10 times, the corresponding washing effect may not be obtained, so it is preferably about 1 to 5 times.

[0187] Furthermore, the reaction product after the liquid separation operation can also be recovered in the form of powder by concentrating the solvent to dryness or performing a crystallization operation under reduced pressure or normal pressure, but in order to improve the operability when preparing the organic film forming material, it can also be prepared in advance into a solution state of appropriate concentration. The concentration at this time is preferably 0.1 to 50% by weight, and more preferably 0.5 to 30% by weight. If it is such a concentration, the viscosity is not easy to increase, thereby preventing damage to the operability, and the amount of the solvent will not be too large, so it is economical.

[0188] The solvent in this case is not particularly limited as long as it can dissolve the compound. Specific examples include: ketones such as cyclohexanone and methyl-2-pentyl ketone; alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, and 1-ethoxy-2-propanol; ethers such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, and diethylene glycol dimethyl ether; esters such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, and propylene glycol mono-tert-butyl ether acetate. These can be used alone or in combination of two or more.

[0189] The imidization of the amic acid shown in step 2 can be synthesized by thermal imidization or chemical imidization. These methods can be appropriately selected according to the thermal stability of the crosslinking group of the target imide compound and the reactivity of the introduced substituent with the reagent used in the chemical imidization.

[0190] When thermal imidization is carried out, the reaction solution of the amic acid compound obtained in step 1 or, when recovered in the form of powder, the amic acid compound is previously dissolved in a soluble solvent, a solvent capable of azeotropy with water is added, and the mixture is heated to 100°C to 250°C to carry out imidization by a dehydration ring-closure reaction while removing the generated water.

[0191] The solvent at this time may be esters such as γ-butyrolactone, polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, N,N-dimethylformamide, and non-polar solvents such as benzene, toluene, xylene, and mesitylene. It is preferred to use these solvents alone or in combination and heat them, and dehydrate them while distilling the water generated by the ring closure to the outside of the system. These solvents may be used in an amount of 0 to 2000 parts by mass relative to 100 parts by mass of the reaction raw materials.

[0192] In the case of chemical imidization, a base catalyst and an acid anhydride as a dehydrating agent are added to the reaction solution of the amic acid compound obtained in step 1 or, if recovered as a powder, the amic acid compound is dissolved in a soluble solvent in advance, and the mixture is heated to 0°C to 120°C for imidization.

[0193] The base catalyst used in chemical imidization can be exemplified by pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc. Among them, pyridine has the appropriate alkalinity required for the reaction to proceed, so it is preferred. The dehydrating agent can be exemplified by acetic anhydride, trimellitic anhydride, pyromellitic anhydride, trifluoroacetic anhydride, polyphosphoric acid, phosphorus pentoxide, phosphorus pentachloride, thionyl chloride, etc., and acetic anhydride is preferably used from the perspective of purification after the reaction. The amount of the catalyst used is 0.1 to 20 moles relative to the molar number of the acid dianhydride of the raw material, preferably in the range of 0.2 to 10 moles. In addition, the base catalyst and the dehydrating agent can be used alone or in combination of two or more, and these can be appropriately controlled by adjusting the amount of catalyst, the amount of dehydrating agent, the reaction temperature, and the reaction time according to the required performance of the target compound.

[0194] The solvent used at this time is not particularly limited as long as it is a solvent inert to the above reaction, and examples thereof include ethers such as diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and 1,4-dioxane, chlorine-based solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene, hydrocarbons such as hexane, heptane, benzene, toluene, xylene, and cumene, nitriles such as acetonitrile, ketones such as acetone, ethyl methyl ketone, isobutyl methyl ketone, and cyclohexanone, esters such as methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol methyl ether acetate, and γ-butyrolactone, and aprotic polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, N,N-dimethylformamide, and hexamethylphosphoric acid triamide, and the like, and they can be used alone or in combination. These solvents can be used in an amount of 0 to 2000 parts by mass relative to 100 parts by mass of the reaction raw materials.

[0195] These imidized compounds can be recovered by the same method as the above-mentioned method for recovering the amic acid compound.

[0196] When preparing the above-mentioned amic acid or imide compound, tetracarboxylic dianhydride and aniline derivatives can be combined according to the required performance. Specifically, substituents that contribute to the improvement of solvent solubility, adhesion, and filling / planarization characteristics, substituents that contribute to etching resistance and film forming properties, etc. can be used in response to the desired required performance. Organic film forming materials using these compounds can take into account both filling / planarization characteristics and heat resistance in a high dimension.

[0197] In addition, as another method for obtaining the organic film-forming compound of the present invention, the following method can also be cited: after obtaining an amic acid compound by reacting tetracarboxylic dianhydride with an aniline derivative having a hydroxyl group (STEP 1), obtaining an imide compound by thermal imidization or chemical imidization (STEP 2), and then converting the hydroxyl group into OR1 (STEP 3). In the following formula, n1, n2, W1, and R1 are the same as those described above.

[0198] [Chemistry 27]

[0199] (STEP1)

[0200]

[0201] (STEP2)

[0202]

[0203] (STEP3)

[0204]

[0205] The reaction for introducing the substituent is not particularly limited as long as it is a method that can introduce R1 into the hydroxyl group, and examples thereof include the following substitution reaction using a halide or toluenesulfonate, mesylate and a base catalyst. In the following formula, n1, n2, W1, and R1 are the same as those described above, and X represents a halogen, toluenesulfonyl or mesylate.

[0206] [Chemistry 28]

[0207]

[0208] The above-mentioned alkaline catalyst used can be sodium bicarbonate, sodium carbonate, potassium carbonate, calcium carbonate, cesium carbonate, sodium hydroxide, potassium hydroxide, sodium hydride, potassium phosphate and other inorganic base compounds, triethylamine, pyridine, N-methylmorpholine and other organic amine compounds, etc., which can be used alone or in combination of two or more. The amount of the catalyst used is 0.1 to 20 moles relative to the molar number of the imide compound of the raw material, preferably in the range of 0.2 to 10 moles.

[0209] The solvent used at this time is not particularly limited as long as it is a solvent that is inert to the above reaction. For example, ether solvents such as diethyl ether, tetrahydrofuran, and dioxane, aromatic solvents such as benzene, toluene, and xylene, acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, water, etc., can be used alone or in combination. These solvents can be used in a range of 0 to 2000 parts by mass relative to 100 parts by mass of the reaction raw materials. The reaction temperature is preferably -50°C to about the boiling point of the solvent, preferably room temperature to 150°C. The reaction time is appropriately selected from 0.1 to 100 hours.

[0210] The obtained compound can be recovered by the same method as the above-mentioned method for recovering the amic acid compound.

[0211] When preparing the organic film-forming compound obtained by this method, various halides, toluene sulfonates and mesylates can be used alone or in combination according to the required performance. For example, a substituent that contributes to the improvement of adhesion to the substrate, the filling / planarization characteristics, a substituent that improves the curing performance, etc. can be introduced in any proportion. Therefore, the organic film-forming material using these compounds can adjust the filling / planarization characteristics, adhesion, curing performance, etching resistance, etc. according to the required performance.

[0212] As described above, the compound for forming an organic film of the present invention provides an organic film forming material that can harden and produce no by-products even under film forming conditions in a passive gas that prevents corrosion of the substrate, and can form an organic film that has good adhesion to the substrate and has heat resistance of, for example, above 400°C and a high degree of filling / planarization properties.

[0213] In the present invention, the planarization property refers to the ability to planarize the surface of a substrate. Figure 1 As shown, by coating the organic film forming material 3' on the substrate 1 and heating it to form the organic film 3, the height difference of the substrate 1 of 100nm can be reduced to less than 30nm. Figure 1 The illustrated stepped shape is a typical example of the stepped shape of a substrate for manufacturing a semiconductor device, and the stepped shape of a substrate that can be flattened by a material containing the compound for forming an organic film of the present invention is of course not limited to this.

[0214] <Organic film forming material>

[0215] The present invention also provides an organic film-forming material, comprising (A) the organic film-forming compound of the present invention and (B) an organic solvent. In the organic film-forming material of the present invention, the organic film-forming compound of the present invention can be used alone or in combination of two or more. The organic film-forming material of the present invention can also be referred to as an organic film-forming composition.

[0216] The organic solvent that can be used in the organic film-forming material of the present invention is not particularly limited as long as it can dissolve the organic film-forming compound of the present invention and the acid generator, crosslinking agent, other additives, etc. as optional components. Specifically, a solvent having a boiling point of less than 180° C. such as the solvents described in paragraphs (0091) to (0092) of Japanese Patent Application Laid-Open No. 2007-199653 can be used. Among them, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, 2-heptanone, cyclopentanone, cyclohexanone, and a mixture of two or more thereof are preferably used.

[0217] Such a material can be applied by spin coating, and since it contains the organic film-forming compound of the present invention as described above, it can be an organic film-forming material having both heat resistance of 400° C. or higher and high filling / planarization properties.

[0218] In addition, in the organic film forming material of the present invention, as for the organic solvent, a high boiling point solvent having a boiling point of 180°C or higher (a mixture of a solvent having a boiling point of less than 180°C and a solvent having a boiling point of 180°C or higher) may be added to the above-mentioned solvent having a boiling point of less than 180°C. The high boiling point organic solvent is not particularly limited as long as it can dissolve the organic film forming compound, and may be a hydrocarbon, alcohol, ketone, ester, ether, chlorine-based solvent, etc. Specific examples include 1-octanol, 2-ethylhexanol, 1-nonanol, 1-decanol, 1-undecanol, ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, 2-ethyl-1,3-hexanediol, etc. Alcohol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, glycerol, n-nonyl acetate, ethylene glycol monohexyl ether, ethylene glycol mono-2-ethylhexyl ether, ethylene glycol monophenyl ether, ethylene glycol monobenzyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol monoisobutyl ether, diethylene glycol monohexyl ether, diethylene glycol monophenyl ether, diethylene glycol monobenzyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol triethylene glycol monomethyl ether, triethylene glycol n-butyl ether, triethylene glycol butyl methyl ether, triethylene glycol diacetate, tetraethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol mono-n-butyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, triacetin, propylene glycol Glycol diacetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol methyl n-propyl ether, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butanediol diacetate, 1,6-hexanediol diacetate, triethylene glycol diacetate, γ-butyrolactone, dihexyl malonate, diethyl succinate, dipropyl succinate, dibutyl succinate, dihexyl succinate, dimethyl adipate, diethyl adipate, dibutyl adipate, etc., which can be used alone or in combination.

[0219] The boiling point of the high boiling point solvent is appropriately selected in accordance with the temperature at which the organic film forming material is subjected to heat treatment. The boiling point of the added high boiling point solvent is preferably 180°C to 300°C, more preferably 200°C to 300°C. If it is such a boiling point, there is no risk of volatilization too quickly during baking (heat treatment) due to too low a boiling point, so sufficient thermal fluidity can be obtained. In addition, if it is such a boiling point, there is no situation where the high boiling point does not volatilize after baking and remains in the film, so there is no risk of adversely affecting the film properties such as etching resistance.

[0220] When the high boiling point solvent is used, the amount of the high boiling point solvent blended is preferably 1 to 30 parts by mass relative to 100 parts by mass of the solvent having a boiling point of less than 180° C. If the blended amount is such, there is no risk that the blended amount is too small and sufficient thermal fluidity cannot be imparted during baking, or that the blended amount is too large and remains in the film, causing the film physical properties such as etching resistance to deteriorate.

[0221] Such an organic film forming material can provide thermal fluidity by adding a high boiling point solvent to the organic film forming compound, thereby achieving an organic film forming material having both high filling and planarizing properties.

[0222] In order to further promote the curing reaction, an acid generator as component (C) may be added to the organic film forming material of the present invention. Acid generators may generate acid by thermal decomposition or by light irradiation, and both may be added. Specifically, materials described in paragraphs (0061) to (0085) of Japanese Patent Publication No. 2007-199653 may be added, but are not limited thereto.

[0223] The acid generators may be used alone or in combination of two or more. The amount of the acid generator added is preferably 0.05 to 50 parts, more preferably 0.1 to 10 parts, based on 100 parts of the compound.

[0224] The organic film-forming material of the present invention may contain a surfactant as the component (D) in order to improve coating properties during spin coating. For example, the surfactant described in (0142) to (0147) of JP-A-2009-269953 may be used.

[0225] In addition, in the organic film forming material of the present invention, in order to improve the hardening property and further suppress the cross-mixing with the upper film, a cross-linking agent as component (E) may also be added. The cross-linking agent is not particularly limited, and cross-linking agents of various known systems can be widely used. As an example, melamine cross-linking agents, glycoluril cross-linking agents, benzoguanamine cross-linking agents, urea cross-linking agents, β-hydroxyalkylamide cross-linking agents, isocyanurate cross-linking agents, aziridine cross-linking agents, oxazoline cross-linking agents, and epoxy cross-linking agents can be exemplified.

[0226] As melamine-based crosslinking agents, specifically, hexamethoxymethylated melamine, hexabutoxymethylated melamine, their alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be exemplified. As glycoluril-based crosslinking agents, specifically, tetramethoxymethylated glycoluril, tetrabutoxymethylated glycoluril, their alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be exemplified. As benzoguanamine-based crosslinking agents, specifically, tetramethoxymethylated benzoguanamine, tetrabutoxymethylated benzoguanamine, their alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be exemplified. As urea-based crosslinking agents, specifically, dimethoxymethylated dimethoxyethylene urea, its alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be exemplified. As β-hydroxyalkylamide-based crosslinking agents, specifically, N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide can be exemplified. Specific examples of isocyanurate crosslinking agents include triglycidyl isocyanurate and triallyl isocyanurate. Specific examples of aziridine crosslinking agents include 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane and 2,2-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate]. Specific examples of the oxazoline crosslinking agent include 2,2'-isopropylidenebis(4-benzyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-methylenebis-4,5-diphenyl-2-oxazoline, 2,2'-methylenebis-4-phenyl-2-oxazoline, 2,2'-methylenebis-4-tert-butyl-2-oxazoline, 2,2'-bis(2-oxazoline), 1,3-phenylenebis(2-oxazoline), 1,4-phenylenebis(2-oxazoline), and 2-isopropenyloxazoline copolymers. Specific examples of the epoxy crosslinking agent include diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, poly(glycidyl methacrylate), trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether.

[0227] In addition, in order to further improve the planarization / burying characteristics, a plasticizer as component (F) may be added to the organic film forming material of the present invention. The plasticizer is not particularly limited, and plasticizers of various known systems can be widely used. As an example, low molecular weight compounds such as phthalates, adipic acid esters, phosphates, trimellitic acid esters, and citrates, polyethers, polyesters, and polymers such as polyacetal polymers described in Japanese Patent Application Laid-Open No. 2013-253227 can be exemplified.

[0228] In the organic film forming material of the present invention, as an additive for imparting the embedding / planarizing property similarly to the plasticizer, for example, a liquid additive having a polyethylene glycol or polypropylene glycol structure, or a thermally decomposable polymer having a weight loss rate of 40% by mass or more between 30° C. and 250° C. and a weight average molecular weight of 300 to 200,000 is preferably used. The thermally decomposable polymer preferably contains a repeating unit having an acetal structure represented by the following general formula (DP1) or (DP1a).

[0229] [Chemistry 29]

[0230]

[0231] In the formula, R6 is a hydrogen atom or a saturated or unsaturated monovalent organic group having 1 to 30 carbon atoms which may be substituted. Y1 is a saturated or unsaturated divalent organic group having 2 to 30 carbon atoms.

[0232] [Chemistry 30]

[0233]

[0234] In the formula, R 6a Y is an alkyl group having 1 to 4 carbon atoms. a It is a saturated or unsaturated divalent hydrocarbon group having 4 to 10 carbon atoms, and may have an ether bond. n represents the average number of repeating units, and is 3 to 500.

[0235] As described above, the organic film forming material of the present invention is a material for forming an organic film that hardens even under film forming conditions in a passive gas that prevents corrosion of the substrate and does not produce byproducts, has good adhesion to the substrate, and has both heat resistance of, for example, 400°C or more and high-level filling / planarization characteristics. Therefore, the organic film forming material of the present invention is extremely useful as an organic film forming material for a multilayer resist method such as a two-layer resist method, a three-layer resist method using a silicon-containing resist intermediate film or an inorganic hard mask (e.g., a silicon-containing inorganic hard mask), and a four-layer resist method using a silicon-containing resist intermediate film or an inorganic hard mask and an organic anti-reflection film. In addition, the organic film forming material of the present invention does not produce byproducts even under film forming conditions in a passive gas and has excellent filling / planarization characteristics, so it can also be ideally used as a planarization material in a semiconductor device manufacturing step other than the multilayer resist method. That is, the organic film forming material of the present invention can be ideally used in a semiconductor device manufacturing step.

[0236] <Substrate for semiconductor device manufacturing>

[0237] The present invention also provides a substrate for manufacturing a semiconductor device, wherein an organic film is formed on the substrate by curing the organic film-forming material of the present invention.

[0238] The semiconductor device manufacturing substrate of the present invention can be said to include a substrate and an organic film formed on the substrate and being a cured product of the organic film-forming material of the present invention.

[0239] Such a substrate for semiconductor device manufacturing contains an organic film having high heat resistance, good adhesion to the substrate, and high filling / planarization properties. Therefore, if it is used in the manufacturing steps of semiconductor devices, the yield of the semiconductor devices will become good.

[0240] <Organic film formation method>

[0241] The present invention further provides a method for forming an organic film suitable for use in a semiconductor device manufacturing process, using the organic film-forming material of the present invention.

[0242] In the method for forming an organic film of the present invention, first, the material for forming an organic film of the present invention is spin-coated (spin-coated) on a substrate to be processed.

[0243] In the method for forming an organic film of the present invention, next, the substrate to be processed, on which the organic film-forming material is applied, is subjected to heat treatment (heat film-forming step) to obtain a cured film.

[0244] The heating film-forming step for forming the hardened film may use a single-stage baking, a double-stage baking, or a multi-stage baking of three or more stages, but a single-stage baking or a double-stage baking is economically preferable.

[0245] Film formation using one-stage baking is preferably carried out at a temperature of 50°C to 600°C for 5 seconds to 7200 seconds, preferably at a temperature of 150°C to 500°C for 10 to 7200 seconds (more preferably 10 to 3600 seconds). By heat treating under such conditions, flattening and cross-linking reactions caused by thermal flow can be promoted. In the multilayer resist method, a coating-type silicon-containing resist intermediate film and a CVD hard mask are sometimes formed on the obtained film. When using a coating-type silicon-containing resist intermediate film, it is preferable to form the film at a temperature higher than the temperature at which the silicon-containing resist intermediate film is formed. Usually, the silicon-containing resist intermediate film is formed at a temperature of 100°C to 400°C, preferably at a temperature of 150°C to 350°C. When the organic film is formed at a temperature higher than this temperature, dissolution of the organic film due to the silicon-containing resist interlayer material can be prevented, and an organic film that is not mixed with the material can be formed.

[0246] When a CVD hard mask is used, it is preferable to form the organic film at a temperature higher than the temperature at which the CVD hard mask is formed. The temperature at which the CVD hard mask is formed may be 150° C. to 500° C., for example.

[0247] In addition, as for the gas environment during baking, inert gases such as nitrogen, argon, and helium can be exemplified. If the material of the present invention is calcined in such an inert gas environment, a fully hardened organic film can be formed without generating sublimates. Moreover, if the material of the present invention is calcined under film forming conditions in an inert gas that prevents corrosion of the substrate, it can be hardened without generating byproducts.

[0248] That is, one aspect of the method for forming an organic film of the present invention is a method for forming an organic film, which is an organic film forming method suitable for the manufacturing steps of a semiconductor device, and is characterized in that: the organic film forming material of the present invention is spin-coated on a substrate to be processed, and the substrate to be processed coated with the organic film forming material is heat-treated in an inert gas environment at a temperature of not less than 50° C. and not more than 600° C. for a period of 5 seconds to 7200 seconds to obtain a cured film.

[0249] On the other hand, in film formation using two-step baking, for example, a first step baking of heat-treating a substrate coated with the organic film-forming material of the present invention in air and a subsequent second step baking in an inert gas atmosphere may be performed.

[0250] Regarding the first stage baking, if the influence of corrosion of the substrate caused by oxygen in the air is considered, the upper limit of the treatment temperature in the air is below 300°C, preferably below 250°C, and is performed in the range of 5 to 600 seconds. The lower limit of the treatment temperature in the air can be, for example, 50°C.

[0251] As for the gas environment in the second stage of baking, inert gases such as nitrogen, argon, and helium can be exemplified. If the material of the present invention is calcined in such an inert gas environment, a fully hardened organic film can be formed without generating sublimates. Furthermore, if the material of the present invention is calcined under film forming conditions in an inert gas that prevents corrosion of the substrate, it can be hardened without generating by-products.

[0252] As for the baking temperature of the second stage, it is preferably higher than the baking temperature of the first stage, for example, at a temperature of 200°C or more and 600°C or less, preferably 500°C or less, in the range of 10 to 7200 seconds. In the multilayer resist method, a coating type silicon-containing resist intermediate film and a CVD hard mask are sometimes formed on the obtained film. When using a coating type silicon-containing resist intermediate film, it is preferable to form the film at a temperature higher than the temperature at which the silicon-containing resist intermediate film is formed. Usually, the silicon-containing resist intermediate film is formed at a temperature of 100°C or more and 400°C or less, preferably 150°C or more and 350°C or less. If the organic film is formed at a temperature higher than this temperature, the dissolution of the organic film caused by the silicon-containing resist intermediate film material can be prevented and an organic film that does not mix with the material can be formed.

[0253] When a CVD hard mask is used in the two-step baking, it is preferable to form the organic film at a temperature higher than the temperature at which the CVD hard mask is formed. The temperature at which the CVD hard mask is formed may be 150° C. to 500° C., for example.

[0254] That is, one aspect of the method for forming an organic film of the present invention is a method for forming an organic film, which is an organic film forming method suitable for the manufacturing step of a semiconductor device, and is characterized by: spin-coating the organic film forming material of the present invention on a processed substrate, heat-treating the processed substrate coated with the organic film forming material in air at a temperature of not less than 50°C and not more than 300°C for a period of 5 seconds to 600 seconds to form a coating film, and then heat-treating the substrate in an inert gas environment at a temperature of not less than 200°C and not more than 600°C for a period of 10 seconds to 7200 seconds to obtain a cured film.

[0255] The oxygen concentration in the above-mentioned inert gas is preferably 1% or less.

[0256] The organic film forming material of the present invention can be sufficiently hardened without generating sublimates even when heated (heat treated) in such an inert gas environment, and can form an organic film having excellent adhesion to the substrate. Furthermore, by heating in such an inert gas environment, corrosion of the substrate being processed can be prevented.

[0257] That is, the present invention provides a method for forming an organic film, which is an organic film used in the manufacturing step of a semiconductor device. In order to prevent corrosion of a processed substrate, the aforementioned heat treatment in a passivation gas environment is to heat treat the processed substrate in a gas environment with an oxygen concentration of less than 1% to form a hardened film.

[0258] In the method for forming the organic film, first, the organic film forming material of the present invention is spin-coated on the substrate to be processed. After spin-coating, if two-stage baking is performed, the baking is first performed in air at a temperature below 300° C., and then the second-stage baking is performed in a gas atmosphere with an oxygen concentration of less than 1%. If it is a single-stage baking, the first stage of baking in air can be skipped. In addition, as the gas atmosphere during baking, inert gases such as nitrogen, argon, and helium can be exemplified. If the material of the present invention is calcined in such an inert gas environment, a fully hardened organic film can still be formed without generating sublimates.

[0259] In addition, the method for forming an organic film of the present invention can use a substrate to be processed that has a structure or a height difference of 30 nm or more. As described above, the material for forming an organic film of the present invention has excellent filling / flattening properties, so even if the substrate to be processed has a structure or a height difference (concave and convex) of 30 nm or more, a flat hardened film can still be formed. That is, the method for forming an organic film of the present invention is particularly useful when forming a flat organic film on such a substrate to be processed.

[0260] Furthermore, the thickness of the formed organic film can be appropriately selected, and is preferably 30 to 20,000 nm, and more preferably 50 to 15,000 nm.

[0261] Furthermore, the above-mentioned method for forming an organic film can be applied to both the case of forming an organic film for an organic film and the case of forming an organic film for a planarizing film using the organic film-forming material of the present invention.

[0262] For example, a variation of the method for forming an organic film of the present invention is a method for forming an organic film, which is a method for forming an organic film that can flatten the surface of a height difference substrate used in the manufacturing step of a semiconductor device, by spin-coating the above-mentioned organic film forming material of the present invention on a processed substrate, heat-treating the processed substrate coated with the organic film forming material in air at a temperature of not less than 50°C and not more than 300°C for 5 to 600 seconds, and then heat-treating it in an inert gas environment at a temperature of not less than 200°C and not more than 600°C for 10 to 7200 seconds, thereby forming a cured film.

[0263] In the method for forming the organic film, first, the organic film forming material of the present invention is spin-coated (spin-coated) on the substrate to be processed. By using the spin coating method, good filling characteristics can be obtained. After spin coating, baking (heat treatment) is performed to promote flattening and cross-linking reactions caused by heat flow. In addition, by this baking, the solvent in the material can be evaporated, so when forming a resist upper film and a silicon-containing resist intermediate film on the organic film, mixing can also be prevented.

[0264] <Pattern Formation Method>

[0265] [Three-layer resist method using a silicon-containing resist interlayer]

[0266] Furthermore, the present invention provides a pattern forming method, characterized in that: an organic film is formed on a workpiece using the organic film forming material of the present invention, a silicon-containing resist intermediate film is formed on the organic film using a silicon-containing resist intermediate film material, a resist upper film is formed on the silicon-containing resist intermediate film using a photoresist composition, a circuit pattern is formed on the resist upper film, the resist upper film with the pattern formed is used as a mask to etch the silicon-containing resist intermediate film, and the pattern is transferred to the silicon-containing resist intermediate film, the silicon-containing resist intermediate film with the transferred pattern is used as a mask to etch the organic film, and the pattern is transferred to the organic film, and the organic film with the transferred pattern is further used as a mask to etch the workpiece, and the pattern is transferred to the workpiece.

[0267] As for the processed body, it is preferable to use a semiconductor device substrate, or a film formed on the semiconductor device substrate of any one of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film. More specifically, without particular limitation, Si, α-Si, p-Si, SiO2, SiN, SiON, W, TiN, Al and other substrates can be used, and the above-mentioned metal films as the processed layer can be formed on the substrate, etc.

[0268] As for the processed layer, various Low-k films such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, Al-Si and their barrier films can be used, which can usually be formed to a thickness of 50 to 10,000 nm, and particularly can be formed to a thickness of 100 to 5,000 nm. In addition, when forming the processed layer, different materials can be used for the substrate and the processed layer.

[0269] In addition, the metal constituting the processed body is preferably silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof.

[0270] Furthermore, a substrate to be processed having a structure with a height of 30 nm or more or a height difference can be used as the object to be processed.

[0271] When an organic film is formed on a workpiece using the organic film-forming material of the present invention, the organic film-forming method of the present invention may be used.

[0272] Then, a resist interlayer film (silicon-containing resist interlayer film) is formed on the organic film using a resist interlayer film material containing silicon atoms. The silicon-containing resist interlayer film material is preferably a polysiloxane-based interlayer film material. By providing the silicon-containing resist interlayer film with an anti-reflection effect, reflection can be suppressed. Especially for 193nm exposure, if a material containing many aromatic groups and having a high etching selectivity with the substrate is used as the material for forming the organic film, the k value will increase and the substrate reflection will become higher, but by providing the silicon-containing resist interlayer film with an absorption that will become an appropriate k value, reflection can be suppressed and the substrate reflection can be reduced to less than 0.5%. As a silicon-containing resist intermediate film with an anti-reflective effect, for 248nm and 157nm exposure, it is preferable to use a polysiloxane having anthracene in a pendant structure or a polysiloxane structure and being cross-linked by acid or heat. For 193nm exposure, it is preferable to use a polysiloxane having a light-absorbing group containing phenyl or silicon-silicon bond in a pendant structure or a polysiloxane structure and being cross-linked by acid or heat.

[0273] Then, a resist upper film is formed on the silicon-containing resist intermediate film using a resist upper film material composed of a photoresist composition. The resist upper film material can be positive or negative, and can use the same photoresist composition as commonly used. It is preferred that the resist upper film material be spin-coated and then pre-baked at 60 to 180° C. for 10 to 300 seconds. Then, exposure is performed according to the usual method, and post-exposure baking (PEB) and development are further performed to obtain a resist upper film pattern. In addition, the thickness of the resist upper film is not particularly limited, and is preferably 30 to 500 nm, and is particularly preferably 50 to 400 nm.

[0274] Then, a circuit pattern (resist upper film pattern) is formed on the resist upper film. In forming the circuit pattern, it is preferable to form the circuit pattern by photolithography using light with a wavelength of 10 nm to 300 nm, direct drawing using an electron beam, nanoimprinting, or a combination thereof.

[0275] In addition, the exposure light may include high-energy rays with a wavelength of less than 300nm, specifically, far ultraviolet rays, KrF excimer laser (248nm), ArF excimer laser (193nm), F2 laser (157nm), Kr2 laser (146nm), Ar2 laser (126nm), 3 to 20nm soft X-rays (EUV), electron beams (EB), ion beams, X-rays, etc.

[0276] In the formation of the circuit pattern, it is preferable to develop the circuit pattern using an alkali or an organic solvent.

[0277] Then, the silicon-containing resist intermediate film is etched using the resist upper film having the circuit pattern as a mask, and the pattern is transferred to the silicon-containing resist intermediate film. The etching of the silicon-containing resist intermediate film using the resist upper film pattern as a mask is preferably performed using a fluorocarbon gas. Thus, a silicon-containing resist intermediate film pattern is formed.

[0278] Then, the silicon-containing resist intermediate film with the transferred pattern is used as a mask to etch the organic film, and the pattern is transferred to the organic film. The silicon-containing resist intermediate film shows higher etching resistance to oxygen or hydrogen than the organic film, so the etching of the organic film using the silicon-containing resist intermediate film pattern as a mask is preferably performed using an etching gas mainly composed of oxygen or hydrogen. In this way, an organic film pattern can be formed.

[0279] Then, the organic film with the transferred pattern is used as a mask to etch the workpiece, and the pattern is transferred to the workpiece. The subsequent etching of the workpiece (the processed layer) can be carried out according to the usual method. For example, if the workpiece is a SiO2, SiN, or silicon dioxide-based low-dielectric constant insulating film, etching is performed mainly using a fluorine (flon) gas. If it is p-Si, Al, or W, etching is performed mainly using a chlorine or bromine gas. When the substrate processing is performed by etching using a fluorine gas, the silicon-containing resist intermediate film pattern will be peeled off at the same time as the substrate processing. On the other hand, when the substrate processing is performed by etching using a chlorine or bromine gas, in order to peel off the silicon-containing resist intermediate film pattern, dry etching stripping using a fluorine gas must be performed separately after the substrate processing.

[0280] The organic film obtained by using the organic film-forming material of the present invention can be excellent in etching resistance when etching the workpiece as described above.

[0281] [Four-layer resist method using silicon-containing resist interlayer and organic antireflection film]

[0282] Furthermore, the present invention provides a pattern forming method, characterized in that: an organic film is formed on a workpiece using the organic film forming material of the present invention, a silicon-containing resist intermediate film is formed on the organic film using a silicon-containing resist intermediate film material, an organic anti-reflective film is formed on the silicon-containing resist intermediate film, a resist upper film is formed on the organic anti-reflective film using a photoresist composition to form a four-layer film structure, a circuit pattern is formed on the resist upper film, the organic anti-reflective film and the silicon-containing resist intermediate film are etched using the patterned resist upper film as a mask to transfer the pattern to the organic anti-reflective film and the silicon-containing resist intermediate film, the silicon-containing resist intermediate film to which the pattern is transferred is used as a mask to etch the organic film to transfer the pattern to the organic film, and the workpiece is further etched using the organic film to which the pattern is transferred as a mask to transfer the pattern to the workpiece.

[0283] This method can be performed in the same manner as the above-mentioned three-layer resist method using the silicon-containing resist interlayer film, except that an organic antireflection film (BARC) is formed between the silicon-containing resist interlayer film and the resist upper layer film.

[0284] The organic anti-reflection film can be formed by spin coating using a known organic anti-reflection film material.

[0285] [Three-layer resist method using an inorganic hard mask]

[0286] Furthermore, the present invention provides a pattern forming method using a three-layer resist method using the organic film forming material of the present invention, which is characterized by: forming an organic film on a workpiece using the organic film forming material of the present invention, forming an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the organic film, forming a resist upper film on the inorganic hard mask using a photoresist composition, forming a circuit pattern on the resist upper film, using the resist upper film with the pattern formed as a mask and etching the aforementioned inorganic hard mask to transfer the pattern to the inorganic hard mask, using the inorganic hard mask with the transferred pattern as a mask and etching the aforementioned organic film to transfer the pattern to the organic film, further using the organic film with the transferred pattern as a mask and etching the aforementioned workpiece to transfer the pattern to the workpiece.

[0287] This method can be performed in the same manner as the above-mentioned three-layer resist method using the silicon-containing resist interlayer film, except that an inorganic hard mask is formed on the organic film instead of the silicon-containing resist interlayer film.

[0288] The inorganic hard mask selected from silicon oxide film, silicon nitride film, and silicon oxide nitride film (SiON film) can be formed by CVD method, ALD method, etc. The method for forming silicon nitride film is described in Japanese Patent Application Publication No. 2002-334869, International Publication No. 2004 / 066377, etc. The film thickness of the inorganic hard mask is preferably 5 to 200 nm, more preferably 10 to 100 nm. The inorganic hard mask is preferably a SiON film that has a high effect as an anti-reflective film. The substrate temperature when forming the SiON film is 300 to 500°C, so the organic film must withstand a temperature of 300 to 500°C. The organic film formed using the organic film forming material of the present invention has high heat resistance and can withstand a high temperature of 300 to 500°C, so it can be a combination of an inorganic hard mask formed by CVD method or ALD method and an organic film formed by spin coating method.

[0289] An inorganic hard mask selected from a titanium oxide film and a titanium nitride film can also be formed by a CVD method, an ALD method, or the like.

[0290] [Four-layer resist method using inorganic hard mask and organic anti-reflective film]

[0291] Furthermore, the present invention provides a pattern forming method using a four-layer resist method using the organic film forming material of the present invention, characterized in that an organic film is formed on a workpiece using the organic film forming material of the present invention, an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film is formed on the organic film, an organic antireflection film is formed on the inorganic hard mask, and a resist upper film is formed on the organic antireflection film using a photoresist composition. , and a 4-layer film structure is formed, a circuit pattern is formed on the upper film of the resist, the upper film of the resist with the pattern is used as a mask to etch the aforementioned organic anti-reflective film and the aforementioned inorganic hard mask, and the pattern is transferred to the organic anti-reflective film and the inorganic hard mask, the inorganic hard mask with the transferred pattern is used as a mask to etch the aforementioned organic film, and the pattern is transferred to the organic film, and the organic film with the transferred pattern is further used as a mask to etch the aforementioned workpiece, and the pattern is transferred to the workpiece.

[0292] This method can be performed in the same manner as the above-mentioned three-layer resist method using an inorganic hard mask, except that an organic antireflection film (BARC) is formed between the inorganic hard mask and the resist upper layer film.

[0293] In particular, when a SiON film is used as an inorganic hard mask, the two-layer antireflection film of the SiON film and the BARC can suppress reflection even in immersion exposure with a high NA exceeding 1.0. Another advantage of forming a BARC is that it has the effect of reducing the tailing of the resist upper film pattern directly above the SiON film.

[0294] Here, an example of a pattern forming method using a three-layer resist method of the present invention is shown in Figure 2 (A) to (F). In the case of the three-layer resist method, Figure 2 As shown in (A), an organic film 3 is formed on a processing layer 2 formed on a substrate 1 using the organic film forming material of the present invention, and then a silicon-containing resist intermediate film 4 is formed, and a resist upper film 5 is formed thereon. Figure 2 As shown in (B), the exposed portion 6 of the resist upper layer film 5 is exposed and PEB (post-exposure baking) is performed. Figure 2 (C) is shown, and development is performed to form a resist upper film pattern 5a. Figure 2 As shown in (D), the resist upper film pattern 5a is used as a mask, and the silicon-containing resist intermediate film 4 is dry-etched using a fluorine-based gas to form a silicon-containing resist intermediate film pattern 4a. Figure 2 As shown in (E), after removing the resist upper film pattern 5a, the organic film 3 is subjected to oxygen plasma etching using the silicon-containing resist intermediate film pattern 4a as a mask to form an organic film pattern 3a. Figure 2 As shown in FIG. 5(F), after the silicon-containing resist intermediate film pattern 4a is removed, the processed layer 2 is etched using the organic film pattern 3a as a mask to form a pattern 2a.

[0295] When forming an inorganic hard mask, the silicon-containing resist intermediate film 4 may be replaced with an inorganic hard mask, and when forming a BARC, the BARC may be formed between the silicon-containing resist intermediate film 4 and the resist upper film 5. The etching of the BARC may be performed continuously before the etching of the silicon-containing resist intermediate film 4, or the etching of the silicon-containing resist intermediate film 4 may be performed only after the etching of the BARC, and then the etching device or the like may be changed to perform the etching.

[0296] As described above, according to the pattern forming method of the present invention, a fine pattern can be formed on a workpiece with high precision by using a multilayer resist method.

[0297] Example

[0298] Hereinafter, the present invention will be described in more detail by raising synthesis example, comparative synthesis example, embodiment and comparative example, but the present invention is not limited thereto. In addition, with regard to molecular weight and dispersion degree, obtain the weight average molecular weight (Mw) and the number average molecular weight (Mn) of the polystyrene conversion obtained by gel permeation chromatography (GPC) using tetrahydrofuran as eluent, and obtain dispersion degree (Mw / Mn).

[0299] Synthesis Example Synthesis of Compounds for Forming Organic Films

[0300] In the synthesis of the organic film-forming compounds (A1) to (A9) and the comparative example compounds (R1) to (R3), the following tetracarboxylic dianhydrides: (B1) to (B4) and aniline derivatives (amine compounds): (C1) to (C7) were used.

[0301] Tetracarboxylic dianhydrides:

[0302] [Chemistry 31]

[0303]

[0304] Aniline derivatives:

[0305] [Chemistry 32]

[0306]

[0307] [Synthesis Example 1] Synthesis of Compound (A1)

[0308] [Chemistry 33]

[0309]

[0310] 100 g of N-methylpyrrolidone was added to 30.00 g of tetracarboxylic anhydride (B1), and a uniform solution was prepared at an internal temperature of 40°C under a nitrogen environment. Then, 19.88 g of an amine compound (C1) was added, and the mixture was reacted at an internal temperature of 40°C for 3 hours to obtain an amide acid solution. 200 g of o-xylene was added to the obtained amide acid solution, and the mixture was reacted for 9 hours at an internal temperature of 150°C while removing the generated low-boiling substances and generated water from the system, and dehydration imidization was performed. After the reaction was completed, the mixture was cooled to room temperature and crystallized in 1000 g of methanol. The precipitated crystals were separated by filtration, washed twice with 500 g of methanol, and recovered. The recovered crystals were vacuum dried at 70°C to obtain compound (A1).

[0311] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0312] (A1): Mw=640, Mw / Mn=1.00

[0313] [Synthesis Example 2] Synthesis of Compound (A2)

[0314] [Chemistry 34]

[0315]

[0316] 100 g of N-methylpyrrolidone was added to 30.00 g of tetracarboxylic anhydride (B1), and a uniform solution was prepared at an internal temperature of 40°C under a nitrogen atmosphere. Then, 18.79 g of an amine compound (C2) was added, and the mixture was reacted at an internal temperature of 40°C for 3 hours to obtain an amide acid solution. 200 g of o-xylene was added to the obtained amide acid solution, and the mixture was reacted for 9 hours at an internal temperature of 150°C while removing the generated low-boiling substances and generated water from the system, and dehydration imidization was performed. After the reaction was completed, the mixture was cooled to 50°C, and 20.53 g of potassium carbonate was added to prepare a uniform dispersion. 19.28 g of propargyl bromide was slowly added dropwise, and the mixture was reacted at an internal temperature of 50°C for 24 hours. 100 g of methyl isobutyl ketone and 200 g of pure water were added to the reaction solution to dissolve the precipitated salt, and then the separated water layer was removed. The organic layer was further washed 6 times with 100 g of a 3% nitric acid aqueous solution and 100 g of pure water, and then the organic layer was dried under reduced pressure. After adding 150 g of THF to the residue to prepare a uniform solution, crystallization was performed in 1000 g of methanol. The precipitated crystals were collected by filtration, washed twice with 500 g of methanol and recovered. The recovered crystals were vacuum dried at 70° C. to obtain compound (A2).

[0317] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0318] (A2): Mw=660, Mw / Mn=1.02

[0319] [Synthesis Example 3] Synthesis of Compound (A3)

[0320] [Chemistry 35]

[0321]

[0322] 100 g of N-methylpyrrolidone was added to 30.00 g of tetracarboxylic anhydride (B2), and a uniform solution was prepared at an internal temperature of 40°C under a nitrogen atmosphere. Then, 14.42 g of an amine compound (C3) was added, and the mixture was reacted at an internal temperature of 40°C for 3 hours to obtain an amide acid solution. 200 g of o-xylene was added to the obtained amide acid solution, and the mixture was reacted for 9 hours at an internal temperature of 150°C while removing the generated low-boiling substances and generated water from the system, and dehydration imidization was performed. After the reaction was completed, the mixture was cooled to 50°C, and 35.05 g of potassium carbonate was added to prepare a uniform dispersion. 32.91 g of propargyl bromide was slowly added dropwise, and the mixture was reacted at an internal temperature of 50°C for 24 hours. 100 g of methyl isobutyl ketone and 200 g of pure water were added to the reaction solution to dissolve the precipitated salt, and then the separated water layer was removed. The organic layer was further washed 6 times with 100 g of a 3% nitric acid aqueous solution and 100 g of pure water, and then the organic layer was dried under reduced pressure. After adding 150 g of THF to the residue to prepare a uniform solution, crystallization was performed in 1000 g of methanol. The precipitated crystals were collected by filtration, washed twice with 500 g of methanol and recovered. The recovered crystals were vacuum dried at 70° C. to obtain compound (A3).

[0323] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0324] (A3): Mw=840, Mw / Mn=1.02

[0325] [Synthesis Example 4] Synthesis of Compound (A4)

[0326] [Chemistry 36]

[0327]

[0328] 100 g of N-methylpyrrolidone was added to 30.00 g of tetracarboxylic anhydride (B2), and a uniform solution was prepared at an internal temperature of 40°C under a nitrogen atmosphere. Then, 18.35 g of an amine compound (C5) was added, and the mixture was reacted at an internal temperature of 40°C for 3 hours to obtain an amide acid solution. 200 g of o-xylene was added to the obtained amide acid solution, and the mixture was reacted for 9 hours at an internal temperature of 150°C while removing the generated low-boiling substances and generated water from the system, and dehydration imidization was performed. After the reaction was completed, the mixture was cooled to 50°C, and 17.52 g of potassium carbonate was added to prepare a uniform dispersion. 16.46 g of propargyl bromide was slowly added dropwise, and the mixture was reacted at an internal temperature of 50°C for 24 hours. 100 g of methyl isobutyl ketone and 200 g of pure water were added to the reaction solution to dissolve the precipitated salt, and then the separated water layer was removed. The organic layer was further washed 6 times with 100 g of a 3% nitric acid aqueous solution and 100 g of pure water, and then the organic layer was dried under reduced pressure. After adding 150 g of THF to the residue to prepare a uniform solution, crystallization was performed in 1000 g of methanol. The precipitated crystals were collected by filtration, washed twice with 500 g of methanol and recovered. The recovered crystals were vacuum dried at 70° C. to obtain compound (A4).

[0329] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0330] (A4): Mw=970, Mw / Mn=1.03

[0331] [Synthesis Example 5] Synthesis of Compound (A5)

[0332] [Chemistry 37]

[0333]

[0334] 100 g of N-methylpyrrolidone was added to 30.00 g of tetracarboxylic anhydride (B3), and a uniform solution was prepared at an internal temperature of 40°C under a nitrogen environment. Then, 13.74 g of an amine compound (C1) was added, and the mixture was reacted at an internal temperature of 40°C for 3 hours to obtain an amide acid solution. 200 g of o-xylene was added to the obtained amide acid solution, and the mixture was reacted for 9 hours at an internal temperature of 150°C while removing the generated low-boiling substances and generated water from the system, and dehydration imidization was performed. After the reaction was completed, the mixture was cooled to room temperature and crystallized in 1000 g of methanol. The precipitated crystals were separated by filtration, washed twice with 500 g of methanol, and recovered. The recovered crystals were vacuum dried at 70°C to obtain compound (A5).

[0335] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0336] (A5): Mw=930, Mw / Mn=1.01

[0337] [Synthesis Example 6] Synthesis of Compound (A6)

[0338] [Chemistry 38]

[0339]

[0340] 100 g of N-methylpyrrolidone was added to 30.00 g of tetracarboxylic anhydride (B3), and a uniform solution was prepared at an internal temperature of 40°C under a nitrogen atmosphere. Then, 14.86 g of an amine compound (C4) was added, and the mixture was reacted at an internal temperature of 40°C for 3 hours to obtain an amide acid solution. 200 g of o-xylene was added to the obtained amide acid solution, and the mixture was reacted for 9 hours at an internal temperature of 150°C while removing the generated low-boiling substances and generated water from the system, and dehydration imidization was performed. After the reaction was completed, the mixture was cooled to 50°C, and 14.19 g of potassium carbonate was added to prepare a uniform dispersion. 13.33 g of propargyl bromide was slowly added dropwise, and the mixture was reacted at an internal temperature of 50°C for 24 hours. 100 g of methyl isobutyl ketone and 200 g of pure water were added to the reaction solution to dissolve the precipitated salt, and then the separated water layer was removed. The organic layer was further washed 6 times with 100 g of a 3% nitric acid aqueous solution and 100 g of pure water, and then the organic layer was dried under reduced pressure. After adding 150 g of THF to the residue to prepare a uniform solution, crystallization was performed in 1000 g of methanol. The precipitated crystals were collected by filtration, washed twice with 500 g of methanol and recovered. The recovered crystals were vacuum dried at 70° C. to obtain compound (A6).

[0341] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0342] (A6): Mw=1060, Mw / Mn=1.03

[0343] [Synthesis Example 7] Synthesis of Compound (A7)

[0344] [Chemistry 39]

[0345]

[0346] 100 g of N-methylpyrrolidone was added to 30.00 g of tetracarboxylic anhydride (B3), and a uniform solution was prepared at an internal temperature of 40°C under a nitrogen atmosphere. Then, 14.86 g of an amine compound (C5) was added, and the mixture was reacted at an internal temperature of 40°C for 3 hours to obtain an amide acid solution. 200 g of o-xylene was added to the obtained amide acid solution, and the mixture was reacted for 9 hours at an internal temperature of 150°C while removing the generated low-boiling substances and generated water from the system, and dehydration imidization was performed. After the reaction was completed, the mixture was cooled to 50°C, and 14.19 g of potassium carbonate was added to prepare a uniform dispersion. 13.33 g of propargyl bromide was slowly added dropwise, and the mixture was reacted at an internal temperature of 50°C for 24 hours. 100 g of methyl isobutyl ketone and 200 g of pure water were added to the reaction solution to dissolve the precipitated salt, and then the separated water layer was removed. The organic layer was further washed 6 times with 100 g of a 3% nitric acid aqueous solution and 100 g of pure water, and then the organic layer was dried under reduced pressure. After adding 150 g of THF to the residue to prepare a uniform solution, crystallization was performed in 1000 g of methanol. The precipitated crystals were collected by filtration, washed twice with 500 g of methanol and recovered. The recovered crystals were vacuum dried at 70° C. to obtain compound (A7).

[0347] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0348] (A7): Mw=1040, Mw / Mn=1.04

[0349] [Synthesis Example 8] Synthesis of Compound (A8)

[0350] [Chemistry 40]

[0351]

[0352] 100 g of N-methylpyrrolidone was added to 30.00 g of tetracarboxylic anhydride (B4), and a uniform solution was prepared at an internal temperature of 40°C under a nitrogen atmosphere. Then, 12.86 g of an amine compound (C4) was added, and the mixture was reacted at an internal temperature of 40°C for 3 hours to obtain an amide acid solution. 200 g of o-xylene was added to the obtained amide acid solution, and the mixture was reacted for 9 hours at an internal temperature of 150°C while removing the generated low-boiling substances and generated water from the system, and dehydration imidization was performed. After the reaction was completed, the mixture was cooled to 50°C, and 12.28 g of potassium carbonate was added to prepare a uniform dispersion. 11.53 g of propargyl bromide was slowly added dropwise, and the mixture was reacted at an internal temperature of 50°C for 24 hours. 100 g of methyl isobutyl ketone and 200 g of pure water were added to the reaction solution to dissolve the precipitated salt, and then the separated water layer was removed. The organic layer was further washed 6 times with 100 g of a 3% nitric acid aqueous solution and 100 g of pure water, and then the organic layer was dried under reduced pressure. After adding 150 g of THF to the residue to prepare a uniform solution, crystallization was performed in 1000 g of methanol. The precipitated crystals were collected by filtration, washed twice with 500 g of methanol and recovered. The recovered crystals were vacuum dried at 70° C. to obtain compound (A8).

[0353] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0354] (A8): Mw=1170, Mw / Mn=1.03

[0355] [Synthesis Example 9] Synthesis of Compound (A9)

[0356] [Chemistry 41]

[0357]

[0358] 100 g of N-methylpyrrolidone was added to 30.00 g of tetracarboxylic anhydride (B4), and a uniform solution was prepared at an internal temperature of 40°C under a nitrogen atmosphere. Then, 12.86 g of an amine compound (C5) was added, and the mixture was reacted at an internal temperature of 40°C for 3 hours to obtain an amide acid solution. 200 g of o-xylene was added to the obtained amide acid solution, and the mixture was reacted for 9 hours at an internal temperature of 150°C while removing the generated low-boiling substances and generated water from the system, and dehydration imidization was performed. After the reaction was completed, the mixture was cooled to 50°C, and 12.28 g of potassium carbonate was added to prepare a uniform dispersion. 11.53 g of propargyl bromide was slowly added dropwise, and the mixture was reacted at an internal temperature of 50°C for 24 hours. 100 g of methyl isobutyl ketone and 200 g of pure water were added to the reaction solution to dissolve the precipitated salt, and then the separated water layer was removed. The organic layer was further washed 6 times with 100 g of a 3% nitric acid aqueous solution and 100 g of pure water, and then the organic layer was dried under reduced pressure. After adding 150 g of THF to the residue to prepare a uniform solution, crystallization was performed in 1000 g of methanol. The precipitated crystals were collected by filtration, washed twice with 500 g of methanol and recovered. The recovered crystals were vacuum dried at 70° C. to obtain compound (A9).

[0359] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0360] (A9): Mw=1150, Mw / Mn=1.04

[0361] [Comparative Synthesis Example 1] Synthesis of Compound (R1)

[0362] [Chemistry 42]

[0363]

[0364] 100 g of N-methylpyrrolidone was added to 30.00 g of tetracarboxylic anhydride (B2), and a uniform solution was prepared at an internal temperature of 40°C under a nitrogen environment. Then, 15.81 g of an amine compound (C6) was added, and the mixture was reacted at an internal temperature of 40°C for 3 hours to obtain an amide acid solution. 200 g of o-xylene was added to the obtained amide acid solution, and the mixture was reacted for 9 hours at an internal temperature of 150°C while removing the generated low-boiling substances and generated water from the system, and dehydration imidization was performed. After the reaction was completed, the mixture was cooled to room temperature and crystallized in 1000 g of methanol. The precipitated crystals were separated by filtration, washed twice with 500 g of methanol, and recovered. The recovered crystals were vacuum dried at 70°C to obtain compound (R1).

[0365] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0366] (R1): Mw=820, Mw / Mn=1.01

[0367] [Comparative Synthesis Example 2] Synthesis of Compound (R2)

[0368] [Chemistry 43]

[0369]

[0370] 100 g of N-methylpyrrolidone was added to 30.00 g of tetracarboxylic anhydride (B2), and a uniform solution was prepared at an internal temperature of 40°C under a nitrogen environment. Then, 18.35 g of an amine compound (C5) was added, and the mixture was reacted at an internal temperature of 40°C for 3 hours to obtain an amide acid solution. 200 g of o-xylene was added to the obtained amide acid solution, and the mixture was reacted for 9 hours at an internal temperature of 150°C while removing the generated low-boiling substances and generated water from the system, and dehydration imidization was performed. After the reaction was completed, the mixture was cooled to room temperature and crystallized in 1000 g of methanol. The precipitated crystals were separated by filtration, washed twice with 500 g of methanol, and recovered. The recovered crystals were vacuum dried at 70°C to obtain compound (R2).

[0371] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0372] (R2): Mw=880, Mw / Mn=1.02

[0373] [Comparative Synthesis Example 3] Synthesis of Compound (R3)

[0374] [Chemistry 44]

[0375]

[0376] To 30.00 g of tetracarboxylic anhydride (B3), 120 g of N-methylpyrrolidone was added, and a uniform dispersion was prepared at an internal temperature of 40°C under a nitrogen environment. 8.13 g of an amine compound (C7) previously dissolved in 50 g of N-methylpyrrolidone was slowly added dropwise, and the mixture was reacted at an internal temperature of 40°C for 3 hours. 7.43 g of an amine compound (C5) as a capping agent was added to the obtained reaction solution, and the mixture was further reacted at an internal temperature of 40°C for 3 hours to obtain a polyamic acid solution. 250 g of o-xylene was added to the obtained amic acid solution, and the mixture was reacted for 9 hours at an internal temperature of 150°C while removing the generated low-boiling substances and generated water from the system, and dehydration imidization was performed. After the reaction was completed, the mixture was cooled to room temperature and crystallized in 1000 g of methanol. The precipitated crystals were separated by filtration, washed twice with 500 g of methanol, and recovered. The recovered crystals were vacuum dried at 70°C to obtain compound (R3).

[0377] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0378] (R3): Mw=2980, Mw / Mn=1.63

[0379] The structural formula, weight average molecular weight (Mw) and dispersity (Mw / Mn) of the compounds obtained above are shown in Tables 1 and 2. The structural formula, Mw and Mw / Mn of compounds (R1) to (R3) used in Comparative Examples are also shown in Table 2.

[0380] [Table 1]

[0381]

[0382] [Table 2]

[0383]

[0384] Preparation of organic film-forming materials (UDL-1 to 12, comparative examples UDL-1 to 3)

[0385] The above compounds (A1) to (A9) and (R1) to (R3) were dissolved in a solvent containing 0.1% by mass of a surfactant FC-4430 (manufactured by Sumitomo 3M Co., Ltd.) at the ratio shown in Table 3, and filtered through a 0.1 μm fluororesin filter to prepare organic film-forming materials (UDL-1 to 12, comparative example UDL-1 to 3). Propylene glycol monomethyl ether acetate (PGMEA) was used as a solvent for the preparation of UDL-1 to 9. A mixture of PGMEA and any one of (S1) 1,6-diacetoxyhexane: boiling point 260°C, (S2) γ-butyrolactone: boiling point 204°C, and (S3) tripropylene glycol monomethyl ether: boiling point 242°C as a high boiling point solvent was used as a solvent for the preparation of UDL-1 to 3. Cyclohexanone (CyHO) was used as a solvent for the preparation of comparative UDL-1 to 3.

[0386] [Table 3]

[0387]

[0388] Example 1 Solvent Resistance Measurement (Examples 1-1 to 1-12, Comparative Examples 1-1 to 1-3)

[0389] The organic film-forming materials (UDL-1 to 12, comparative UDL-1 to 3) prepared above were applied on a silicon substrate and fired at 400°C for 60 seconds in a nitrogen flow with an oxygen concentration of 0.2% or less. The film thickness was measured. Apply PGMEA solvent on it, let it stand for 30 seconds and spin dry, bake at 100℃ for 60 seconds to evaporate PGMEA, and measure the film thickness The difference in film thickness before and after the PGMEA treatment was determined (residual film ratio: (b / a)×100). The results are shown in Table 4 below.

[0390] [Table 4]

[0391]

[0392] As shown in Table 4, the organic film forming material of the present invention (Examples 1-1 to 1-12) has a residual film rate of more than 99.5% after PGMEA treatment, which shows that a cross-linking reaction still occurs even in a nitrogen environment and exhibits sufficient solvent resistance. In contrast, Comparative Examples 1-1 and 1-2 do not have a substituent that will become a cross-linking group, so the residual film rate after PGMEA treatment is less than 50%, and no hardening reaction occurs, so solvent resistance is not exhibited. In addition, although the polyimide type Comparative Example 1-3 has a residual film rate of more than 50% after PGMEA treatment due to low solubility, it does not have a cross-linking structure, so sufficient solvent resistance cannot be ensured. From these results, it can be seen that the substituent represented by OR1 introduced as a substituent effectively functions as a thermal cross-linking group.

[0393] Example 2 Evaluation of heat resistance properties (Examples 2-1 to 2-12, Comparative Examples 2-1 to 2-3)

[0394] The organic film-forming materials (UDL-1 to 12, comparative UDL-1 to 3) were coated on a silicon substrate and calcined at 180° C. in air to form a coating film of 200 nm. The film thickness was measured. The substrate was further calcined at 400° C. for 10 minutes in a nitrogen flow with an oxygen concentration controlled to be 0.2% or less, and the film thickness was measured. The residual film ratio was calculated by dividing the film thickness B by the film thickness A. Table 5 shows these results.

[0395] [Table 5]

[0396]

[0397] As shown in Table 5, the organic film forming material of the present invention (Examples 2-1 to 2-12) did not reduce by 3% in film thickness even after calcination at 400°C for 10 minutes. It can be seen that the organic film forming material of the present invention maintains film thickness even after calcination at 400°C and has high heat resistance. For Examples 2-4, 2-6 to 2-12 containing compounds with a naphthalene ring structure in the terminal structure, the film thickness reduction was less than 2%. Among them, the one having a fluorene structure and having OR1 introduced as a crosslinking group at the β position of the naphthalene ring in the terminal structure showed a smaller film thickness reduction. On the other hand, Comparative Examples 2-1 to 2-3 without a crosslinking structure showed a significant film thickness reduction of more than 40% for the monomolecular Comparative Examples 2-1 and 2-2, and a film thickness reduction of more than 15% for the polymer type Comparative Example 2-3. It can be seen from the above results that a dense film and a high heat resistance film are formed not only due to the imide structure but also due to the crosslinking reaction.

[0398] Example 3 Evaluation of landfill characteristics (Examples 3-1 to 3-12, Comparative Examples 3-1 to 3-3)

[0399] like Figure 3 The organic film forming materials (UDL-1 to 12, comparative UDL-1 to 3) were coated on a SiO2 wafer substrate having a dense hole pattern (hole diameter 0.16 μm, hole depth 0.50 μm, and the distance between the centers of two adjacent holes 0.32 μm), and calcined at 400°C for 60 seconds using a hot plate in a nitrogen flow with an oxygen concentration of less than 0.2%, to form an organic film 8. The substrate used was as follows Figure 3 (G) (top view) and (H) (cross-sectional view) show a base substrate 7 (SiO2 wafer substrate) with a dense hole pattern. The cross-sectional shape of each wafer substrate obtained was observed using a scanning electron microscope (SEM) to confirm whether the organic film was filled inside the hole without pores (voids). The results are shown in Table 6. When an organic film forming material with poor filling characteristics was used, pores were generated inside the hole in this evaluation. When an organic film forming material with good filling characteristics was used, in this evaluation, as shown in FIG. Figure 3 As shown in (I), the organic film fills the pores without any gaps.

[0400] [Table 6]

[0401]

[0402] As shown in Table 6, the organic film forming material of the present invention (Examples 3-1 to 3-12) can fill the hole pattern without generating voids, and it can be confirmed that it has good filling characteristics. On the other hand, since Comparative Example 3-3 uses a polymer-type imide compound, the fluidity is insufficient, and voids are confirmed to be generated, and the filling characteristics are poor. Moreover, Comparative Examples 3-1 and 3-2 have insufficient heat resistance as shown in the results of the heat resistance evaluation, but the filling properties are ensured. From these results, it can be confirmed that the organic film forming material of the present invention has good filling characteristics.

[0403] Example 4 Evaluation of planarization characteristics (Examples 4-1 to 4-12, Comparative Examples 4-1 to 4-3)

[0404] The organic film forming materials (UDL-1 to 12, comparative UDL-1 to 3) were applied to the surfaces having the giant isolated trench pattern ( Figure 4 (J), a base substrate 9 (SiO2 wafer substrate) having a groove width of 10 μm and a groove depth of 0.10 μm) was calcined at 400°C for 60 seconds under a nitrogen flow with an oxygen concentration of less than 0.2%, and the height difference of the organic film 10 between the groove part and the non-groove part was observed using an NX10 atomic force microscope (AFM) manufactured by Park Systems. Figure 4(k) in delta10). The results are shown in Table 7. In this evaluation, the smaller the height difference, the better the planarization characteristics. In addition, in this evaluation, a trench pattern with a depth of 0.10 μm was planarized using an organic film forming material with a film thickness of about 0.2 μm, and strict evaluation conditions were used to evaluate the quality of the planarization characteristics.

[0405] [Table 7]

[0406]

[0407] As shown in Table 7, the organic film forming material of the present invention (Examples 4-1 to 4-12) has a smaller height difference between the organic film in the trench part and the non-ditch part than that of Comparative Examples 4-1 to 4-3, and it is confirmed that the flattening property is better. Comparative Examples 4-1 and 4-2 have insufficient heat resistance as shown in the results of the heat resistance evaluation, and their embedding properties are ensured as shown in the embedding property evaluation, but film shrinkage occurs during high-temperature baking, which is the result of deterioration of flattening property. In addition, Comparative Example 4-3 uses a polymer-type imide compound, so its thermal fluidity is insufficient as shown in the results of the embedding property evaluation, so the flattening property is not good. In addition, when Examples 4-10 to 4-12 to which a high boiling point solvent is added are compared with Examples 4-4, 4-7 and 4-9 to which no high boiling point solvent is added, it can be seen that the flattening is further improved due to the addition of a high boiling point solvent. From this result, it can be seen that the organic film forming material of the present invention has excellent heat resistance, so that the film shrinkage during high-temperature baking is suppressed, and excellent flattening property is exhibited.

[0408] Example 5 Pattern Formation Test 1 (Examples 5-1 to 5-12, Comparative Example 5-1)

[0409] The above-mentioned organic film forming materials (UDL-1 to 12, comparative UDL-3) were coated on a silicon wafer substrate with a 300nm SiO2 film formed thereon, and calcined at 400°C for 60 seconds in a nitrogen flow with an oxygen concentration of 0.2% or less to form an organic film (resist lower layer film). A CVD-SiON hard mask was formed thereon, and an organic anti-reflection film material (ARC-29A: manufactured by Nissan Chemical Co., Ltd.) was further coated thereon, and baked at 210°C for 60 seconds to form an organic anti-reflection film with a film thickness of 80nm. A single-layer resist for ArF, which was a resist upper layer film material, was coated thereon, and baked at 105°C for 60 seconds to form a photoresist film with a film thickness of 100nm (resist upper layer film). A wet protection film material (TC-1) was coated on the photoresist film, and baked at 90°C for 60 seconds to form a protection film with a film thickness of 50nm. In addition, in the comparative examples UDL-1 and UDL-2, the heat resistance was poor and a CVD-SiON hard mask could not be formed, so the subsequent patterning test could not be performed.

[0410] As for the resist upper layer film material (single-layer resist for ArF), a polymer (RP1), an acid generator (PAG1), and a basic compound (Amine1) are dissolved in a solvent containing 0.1 mass% of FC-430 (manufactured by Sumitomo 3M Co., Ltd.) according to the ratio in Table 8 and filtered through a 0.1 μm fluororesin filter to prepare it.

[0411] [Table 8]

[0412]

[0413] The polymer (RP1), acid generator (PAG1), and basic compound (Amine1) used are shown below.

[0414] [Chemistry 45]

[0415]

[0416] The wet protective film material (TC-1) was prepared by dissolving the protective film polymer (PP1) in an organic solvent at the ratio in Table 9 and filtering the solution with a 0.1 μm fluororesin filter.

[0417] [Table 9]

[0418]

[0419] The polymer (PP1) used is shown below.

[0420] [Chemistry 46]

[0421]

[0422] Then, exposure was performed using an ArF immersion exposure device (manufactured by Nikon Co., Ltd.; NSR-S610C, NA1.30, σ0.98 / 0.65, 35 degree dipole s-polarized illumination, 6% half-step phase shift mask), baked (PEB) at 100°C for 60 seconds, and developed with a 2.38 mass % tetramethylammonium hydroxide (TMAH) aqueous solution for 30 seconds to obtain a 55nm 1:1 positive line and space pattern.

[0423] Then, using a Tokyo Electron etching device Telius, dry etching was performed using the resist pattern as a mask to etch the organic anti-reflective film and the CVD-SiON hard mask to form a hard mask pattern, the obtained hard mask pattern was used as a mask to etch the organic film to form an organic film pattern, and the obtained organic film pattern was used as a mask to etch the SiO2 film. The etching conditions are as follows.

[0424] Transfer conditions for transferring the resist pattern to the SiON hard mask.

[0425]

[0426] Transfer conditions for transferring the hard mask pattern to the organic film.

[0427]

[0428] Transfer conditions for transferring organic film patterns to SiO2 films.

[0429]

[0430]

[0431] Table 10 shows the results of observing the pattern cross section using an electron microscope (S-4700) manufactured by Hitachi, Ltd.

[0432] [Table 10]

[0433]

[0434] As shown in Table 10, the results of the organic film-forming material of the present invention (Examples 5-1 to 5-12) show that in any of the above cases, the resist upper film pattern is finally well transferred to the substrate, confirming that the organic film-forming material of the present invention can be ideally used for microfabrication using a multilayer resist method. Comparative Example 5-1 has insufficient heat resistance, but can form a pattern.

[0435] In addition, the organic film forming material of the present invention (Examples 5-1 to 5-12) can form an organic film that exhibits excellent adhesion to the substrate, and thus can suppress the film peeling of the CVD-SiON hard mask formed directly above the organic film and the resist upper film formed thereon. As a result, in Examples 5-1 to 5-12, as described above, the resist upper film pattern can be finally well transferred to the substrate.

[0436] Example 6 Pattern Formation Test 2 (Examples 6-1 to 6-12, Comparative Example 6-1)

[0437] The above-mentioned organic film forming materials (UDL-1 to 12, comparison UDL-3) were respectively coated on a SiO2 wafer substrate having a groove pattern (groove width 10 μm, groove depth 0.10 μm), and calcined at 400°C for 60 seconds under a nitrogen flow with an oxygen concentration managed to be below 0.2%. In addition, the coating film was formed in the same manner as in pattern formation test 1, and patterning and dry etching were performed. The shape of the completed pattern was observed, and the results are shown in Table 11.

[0438] [Table 11]

[0439]

[0440] As shown in Table 11, the results of the organic film-forming material of the present invention (Examples 6-1 to 6-12) show that in any of the above cases, the resist upper film pattern is finally well transferred to the substrate, confirming that the organic film-forming material of the present invention can be ideally used in micro-processing using a multilayer resist method. On the other hand, in Comparative Example 6-1, as shown in the results of the flattening property evaluation, the flattening property is poor, so the pattern collapse occurs during pattern processing, and ultimately a good pattern cannot be obtained.

[0441] In addition, the organic film forming material of the present invention (Examples 6-1 to 6-12) can form an organic film that exhibits excellent adhesion to the substrate, and thus can suppress the film peeling of the CVD-SiON hard mask formed directly above the organic film and the resist upper film formed thereon. As a result, in Examples 6-1 to 6-12, as described above, the resist upper film pattern can be finally well transferred to the substrate.

[0442] From the above, it can be seen that if the organic film forming material of the present invention contains the organic film forming compound of the present invention, it still has heat resistance of more than 400°C, excellent adhesion to the substrate and a high degree of filling / planarization characteristics even under an inert gas that does not contain oxygen, so it is extremely useful as an organic film forming material used in a multilayer resist method. In addition, if the pattern forming method of the present invention uses this material, even if the processed body is a substrate with a height difference, a fine pattern can be formed with high precision.

[0443] The present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and those having substantially the same configuration and exhibiting the same functions and effects as the technical concept described in the claims of the present invention are all within the technical scope of the present invention.

[0444] Description of Reference Numerals

[0445] 1:Substrate

[0446] 2: Processing layer

[0447] 2a: Pattern formed on the processed layer

[0448] 3: Organic film

[0449] 3': Organic film forming material

[0450] 3a: Organic film pattern

[0451] 4: Silicon-containing resist interlayer

[0452] 4a: Silicon-containing resist interlayer pattern

[0453] 5: Resist upper film

[0454] 5a: Resist upper film pattern

[0455] 6: Exposure part

[0456] 7: Base substrate with dense hole pattern

[0457] 8: Organic film

[0458] 9: Base substrate with large isolated trench patterns

[0459] 10: Organic film

[0460] delta10: height difference between the organic film in the trench and non-ditch areas

Claims

1. An organic film-forming material, characterized in that it contains: (A) an organic film-forming compound represented by the following general formula (1B), and (B) an organic solvent; In the formula, W2 is an oxygen atom or a divalent group, n1 represents an integer of 0 or 1, n2 represents an integer of 1 to 3, R1 represents an alkynyl group having 2 to 10 carbon atoms, and when n1 is 0, n2 is 2 or 3.

2. The organic film-forming material according to claim 1, wherein W2 in the general formula (1B) is a divalent organic group having at least one aromatic ring.

3. The organic film-forming material according to claim 1 or 2, wherein The component (A) is a compound represented by the following general formula (1C); In the formula, W3 is a divalent organic group, n3 represents an integer of 0 or 1, n1, n2 and R1 are the same as described above, and when n1 is 0, n2 is 2 or 3.

4. The organic film-forming material according to claim 1 or 2, wherein The component (A) is a compound represented by the following general formula (1D); In the formula, n3 represents an integer of 0 or 1, and n2 and R1 are the same as described above.

5. The organic film-forming material according to claim 1 or 2, wherein The ratio Mw / Mn of the weight average molecular weight Mw and the number average molecular weight Mn of the component (A) in terms of polystyrene obtained by gel permeation chromatography is 1.00≤Mw / Mn≤1.

10.

6. The organic film-forming material according to claim 1 or 2, wherein The organic solvent is a mixture of one or more organic solvents having a boiling point of less than 180° C. and one or more organic solvents having a boiling point of 180° C. or higher.

7. The organic film-forming material according to claim 1 or 2, wherein The organic film-forming material further contains one or more of (C) an acid generator, (D) a surfactant, (E) a crosslinking agent, and (F) a plasticizer. 8 . A substrate for manufacturing a semiconductor device, wherein an organic film is formed on a substrate by curing the organic film-forming material according to claim 1 .

9. A method for forming an organic film, which is suitable for a manufacturing step of a semiconductor device, characterized in that: The organic film-forming material according to any one of claims 1 to 7 is spin-coated on a substrate to be processed, The substrate to be processed, on which the organic film-forming material is applied, is heat-treated in an inert gas environment at a temperature of 50° C. to 600° C. for 5 to 7200 seconds to obtain a cured film.

10. A method for forming an organic film, which is suitable for a manufacturing step of a semiconductor device, characterized in that: The organic film-forming material according to any one of claims 1 to 7 is spin-coated on a substrate to be processed, The substrate to be processed, on which the organic film forming material is applied, is heat-treated in air at a temperature of 50° C. to 300° C. for 5 to 600 seconds to form a coating film. Then, heat treatment is performed at a temperature of 200° C. to 600° C. in an inert gas environment for a period of 10 to 7200 seconds to obtain a cured film.

11. The method for forming an organic film according to claim 9 or 10, wherein: The oxygen concentration in the inert gas is 1% or less.

12. The method for forming an organic film according to claim 9 or 10, wherein: As the substrate to be processed, a substrate to be processed having a structure with a height of 30 nm or more or a height difference is used.

13. A pattern forming method, characterized by: forming an organic film on a workpiece using the organic film-forming material according to any one of claims 1 to 7, A silicon-containing resist interlayer film is formed on the organic film using a silicon-containing resist interlayer film material. forming a resist upper film on the silicon-containing resist intermediate film using a photoresist composition, forming a circuit pattern on the upper layer of the resist, The silicon-containing resist intermediate film is etched using the resist upper layer film having the pattern formed thereon as a mask, thereby transferring the pattern to the silicon-containing resist intermediate film. The organic film is etched using the silicon-containing resist intermediate film having the transferred pattern as a mask to transfer the pattern to the organic film. Furthermore, the object to be processed is etched using the organic film to which the pattern is transferred as a mask, thereby transferring the pattern to the object to be processed.

14. A pattern forming method, characterized by: forming an organic film on a workpiece using the organic film-forming material according to any one of claims 1 to 7, A silicon-containing resist interlayer film is formed on the organic film using a silicon-containing resist interlayer film material. forming an organic anti-reflection film on the silicon-containing resist intermediate film, A photoresist composition is used to form a resist upper film on the organic anti-reflection film to form a 4-layer film structure. forming a circuit pattern on the upper layer of the resist, The organic anti-reflection film and the silicon-containing resist intermediate film are etched using the resist upper layer film having the pattern formed thereon as a mask, thereby transferring the pattern to the organic anti-reflection film and the silicon-containing resist intermediate film. The organic film is etched using the silicon-containing resist intermediate film having the transferred pattern as a mask to transfer the pattern to the organic film. Furthermore, the object to be processed is etched using the organic film to which the pattern is transferred as a mask, thereby transferring the pattern to the object to be processed.

15. A method for forming a pattern, characterized by: forming an organic film on a workpiece using the organic film-forming material according to any one of claims 1 to 7, forming an inorganic hard mask film selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the organic film, forming a resist upper layer film on the inorganic hard mask using a photoresist composition, forming a circuit pattern on the upper layer of the resist, The inorganic hard mask is etched using the resist upper layer film having the pattern formed thereon as a mask, thereby transferring the pattern to the inorganic hard mask. The inorganic hard mask having the transferred pattern is used as a mask to etch the organic film, thereby transferring the pattern to the organic film. Furthermore, the object to be processed is etched using the organic film to which the pattern is transferred as a mask, thereby transferring the pattern to the object to be processed.

16. A method for forming a pattern, characterized by: forming an organic film on a workpiece using the organic film-forming material according to any one of claims 1 to 7, forming an inorganic hard mask film selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the organic film, forming an organic anti-reflection film on the inorganic hard mask, A photoresist composition is used to form a resist upper film on the organic anti-reflection film to form a 4-layer film structure. forming a circuit pattern on the upper layer of the resist, The organic anti-reflection film and the inorganic hard mask are etched using the resist upper layer film having the pattern as a mask, thereby transferring the pattern to the organic anti-reflection film and the inorganic hard mask. The inorganic hard mask having the transferred pattern is used as a mask to etch the organic film, thereby transferring the pattern to the organic film. Furthermore, the object to be processed is etched using the organic film to which the pattern is transferred as a mask, thereby transferring the pattern to the object to be processed.

17. The pattern forming method according to claim 15 or 16, wherein: The inorganic hard mask is formed by a CVD method or an ALD method.

18. The pattern forming method according to any one of claims 13 to 16, wherein: In forming the circuit pattern, the circuit pattern is formed by photolithography using light with a wavelength of 10 nm to 300 nm, direct drawing using an electron beam, nanoimprinting, or a combination thereof.

19. The pattern forming method according to any one of claims 13 to 16, wherein: In the formation of the circuit pattern, the circuit pattern is developed using an alkali or an organic solvent.

20. The pattern forming method according to any one of claims 13 to 16, wherein: A semiconductor device substrate or a film formed on the semiconductor device substrate of any one of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film is used as the processed object.

21. The pattern forming method according to claim 20, wherein: As the workpiece, a material containing silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof is used.

22. A compound for forming an organic film, represented by the following general formula (1B); In the formula, W2 is an oxygen atom or a divalent group, n1 represents an integer of 0 or 1, n2 represents an integer of 1 to 3, R1 represents an alkynyl group having 2 to 10 carbon atoms, and when n1 is 0, n2 is 2 or 3.

23. The compound for forming an organic film according to claim 22, wherein W2 in the general formula (1B) is a divalent organic group having at least one aromatic ring.

24. The compound for forming an organic film according to claim 22 or 23, wherein The organic film-forming compound is represented by the following general formula (1C): In the formula, W3 is a divalent organic group, n3 represents an integer of 0 or 1, n1, n2 and R1 are the same as described above, and when n1 is 0, n2 is 2 or 3.

25. The compound for forming an organic film according to claim 22 or 23, wherein The organic film-forming compound is represented by the following general formula (1D): In the formula, n3 represents an integer of 0 or 1, and n2 and R1 are the same as described above.